IMPLIKATUR DALAM KAJIAN PRAGMATIK - -, Mulyana (Diksi, 2015)
<img src="data:image/png;base64,iVBORw0KGgoAAAANSUhEUgAAAb0AAAFqCAIAAAABdxOEAAAgAElEQVR4nOydeTxV2x/3NylERSoNpopUhOZJIY2UlESjKYpCKlEqGqgkhUwlMpV5KFRIomQMKTOZHfN0HM64nz++z93Peej2u+7Q/d3fXe8/emnttdZee+29Puu7vms4GI5AIBCIsYD93QVAIBCIfxhINxEIBGJsIN1EIBCIsYF0E4FAIMYG0k0EAoEYG0g3EQgEYmwg3UQgEIixgXQTgUAgxgbSTQQCgRgbSDcRCARibCDdRCAQiLGBdBOBQCDGBtJNBAKBGBtINxEIBGJsIN1EIBCIsYF0E4FAIMYG0k0EAoEYG0g3EQgEYmwg3UQgEIixgXQTgUAgxgbSTQQCgRgbSDcRCARibCDdRCAQiLGBdBOBQCDGBtJNBAKBGBtINxEIBGJsIN1EIBCIsYF0E4FAIMbGz9BNEomUm5v79evX0tLSr1+/FhcXV1ZWVlVVff78ubW1dXBwsLe3l06nj0jFYrEGBwf7+/sHBgZ6e3vb2tra29t7enp6enoGBgb6+/u7uro6Ozv7+vqIJHQ6vbe3t7OzE1L19fV1dHT09PQwmUwiDoPB6Ovr6+rqIuJ0dnYODQ0NDg729fVBYH9/f29vL4VCgTw7OzsHBwehSBQKhcFg/IRKQyAQ/7X8DN3MyMjQ0NBQVlZWUVFRUVHR1dV98OCBv7//kSNHLCws7t69e/Xq1YSEBBqNRiRhMplfvnxxd3e/cePGzZs3XVxc/P39k5OTExISXF1db968eevWLQ8PD09Pzxs3boSFhVVUVDAYjKGhoczMzPv37zs5OUGcx48fv3v3DlQPGBwcTEtLc3Z2JuIEBgZ++fIlLS2NuJ2jo6Ovr29ZWRmO4x0dHZ6ennfu3ElNTX327FlBQcHw8DD709Hp9Obm5srKShYb9fX1eXl5mZmZ6enpHz9+zM/Pz8/Pz83Nffv27bt373Jycr59+9bS0lJUVJSTk5Ofn5+Xl/fhw4eSkhIWi0Wj0SByVlZWSUkJiUSqqakpLy9vbGxsaGgoKyvLzs4uKyv79u1ba2sriDhxXygSjUZraWmpqqqqr69vaGioq6srLy8vLS1tamqiUqnffUeQnMFg9Pf3Dw4OsudGp9ObmpqI3BoaGioqKurr64eHh4k4o3ODqiaTySPCyWRyX1/f4OAghUIhk8nsXRqRG5VKpVAoFAoFOjD2MjMYjIGBgYGBAQqFAr3d4OAgjUZjsVh0On3wFyACk8n8bglHBI6ovd8Ce/wxJfxBhr8lt99YztFxRhR4dD4/qIQxPemfUhv//fwM3SSTya6uroKCghiGTZw40drauqqqqq2t7fr169OmTcMwDMMwRUXFnJwcIgmdTr9w4cKUKVM4ODg4ODiWLl3q7+9fVVUVHR2toqLCwcHBz8+vr69vb28vLi4+bty4jRs3vn//nslk5ufn6+vrQ6oZM2Z4enrm5+cPDQ0ROVOp1PT09F27dkGc6dOn+/j45OXlPXv2TElJiYuLi4ODg5eX18DAAHSzp6fH1NQUwzAhISE1NbX379+PeLrGxsZDhw4pKip2d3cTgUZGRuPGjZs9e7akpKSAgAAXFxcXFxcvL6+UlJSEhAQ3N7e2tnZAQICmpuakSZO4uLjGjx8/bdo0U1NTHMd7e3t37tzJy8srJCRkbGz8/Pnzy5cvKysr7969e+/evZqamlu2bNHT09u9e7eBgcGLFy/g6dgFqK+vLyws7OjRozt37ty1a9eePXuOHTumr69vZGQUEBBQUVHxa+r55csXJyen169fswdSKJSgoCA9PT3IbefOnXv37vX09Gxra/vBS+/u7n706FFkZCR7IIPByM/PDwoKevDggaen57179969e0f0l9Buu7u7nzx54ubm5unp6ePjEx8f39TUxF6Y9PR0X19fyMHNzS0sLKy5uRnH8ebm5ujoaA8Pj3v37nl5eb158wZGDOzdCYlE6uzsHFFUFosFCtvd3V1VVVVVVVX9C/X19fX19VVVVbW1tbW1tTBO6uvrY1dk6G+6u7vZXwG8kdbWVujhWlpa2O9LpVI7OjpIJFJLS0t7ezuDwSDSMpnMtra2lpaWjo6Ojo4O+LulpYXIH8Zhra2tbW1tHR0d7e3tra2tTU1Nra2tfX19vzYYgmccHh6Gnmx0j8L+3/7+/sbGxpaWFqLbYzAYdDqdxWJBXzU8PDw8PMxu6IzIamhoiEql0mi0H0T7R/OT/JvZ2dnLly/HMGzy5MlPnjyBqszMzJSTkwPd5OHhuXbtGhG/o6Nj1apV2C/o6OjU1NQwmUwSiWRlZYVh2KRJk4KCgjo7O8+ePcvNzY1hmIGBQX19PZ1O9/f3h1QSEhIkEgneN/tXTqPRHj58CHHExcXb2trodPrQ0JCtre3EiRMxDJs1a1ZAQAB8pq2trXZ2djNnzrx7925rayuYNuy5paSkTJgwYdq0aWlpaUS4srKygIBAXFzct2/fDh06RNzr27dvhYWFq1atWrlyZUFBQVpamoyMDIZhAgIC169f7+npwXGcyWTW1taKiYmZmJg0NDQMDQ29f/9+48aNHBwckydPtrW1bW9vT0hIkJOT4+LimjVr1tOnT8HLwV6q9vb2K1eu8PDwcHBwSEtLP3/+PCUlRUlJiZ+fX1ZWNjAw8Ltfs5OTEzc3t7W1NXvzY7FYvb29Dg4OAgIC0KmcP3++ubl5hEyM4PXr1+Li4gYGBuwNksViFRYWnjlzZvbs2Tw8PDw8PCoqKtnZ2UQECoXi4uIyY8YMHh4eXl7e3bt3R0VFtbe3ExFoNFpqaqqamho/Pz8vLy8/P/+xY8dqa2txHK+trTUzMxMQEJg+fbqmpqafn98Ia7eoqEhNTc3MzGxEyYkSxsTErFy5UkhISEBAQFhYWEVFxcLC4vjx4xISEoKCgoKCgjNnzty0adObN29GPGxxcbG5uXl1dTV74NDQ0N27d+fMmTNz5kwlJSUjI6P8/Hy41NjY6OzsrK2tra2t7enpOTAwQKSi0+k+Pj56enq6uroHDx48cuSIoaGhrq7uiRMnkpKSoI8sLCw8d+6cjo7OwYMHDx8+bGBgcOzYsWPHjtnZ2cXExEBtjACeMT09/cGDByOemp329vbMzExnZ+cjR46Ym5tHRUV9/fqVRCLFxcVBtp8/fw4MDAwKCgoICIiKihp9LyaTmZOT8/jx4+Dg4CdPnjx79qyoqGjEvWg0GplMZv8CGQxGV1dXW1tba2sr9G3ghSO6lr6+vqGhoZ6eno6Ojq6uLrja1dVFJpP7+/vhbwjs7OyE21Gp1N7e3q6uLuha+vv7Rz/v7+Yn6WZ+fv7q1avBagsPD4dm+fHjR21tbTk5uVmzZmEYpqGhAQNqCoXi6ekpJSXFwcEBimNgYNDa2orjeF9f38WLFzEMExQUBFsmNTV1/vz5GIZJS0u/evUKx/Hw8HBIJSUlxT5CZ+fZs2ej41y/fl1AQAAEDjKvrq42MjJSUVGJjo5mN1qh98ZxvKmpycTEBMMwLi6uEydOEO9my5YtlpaW8P5u374N91q0aBFcjYiIOHz48JcvXxISEiQkJDAMW7lyJbt8DA8PL1y40MbGBnwCdXV1e/fuxTCMj4/v6tWrEMHJyYmfnx/DsA0bNhQUFIx4QDqd/ujRI+hR1q5dW1paymAwwsPDJSUl4akDAwNHJKFQKHv27IEMiRZOEBcXB69p/vz5SUlJ361VwnCDyoRhxNevX9njUKnU+Ph4eGp4Ind3d/yXZtza2rp06VKiv/T19R0xlsdxfGBgwNPTk4eHB8OwxYsXp6SkQLfR2dl5/vx5UVHRCxcuNDY29vb2EgYa/BEUFMTFxaWgoDC6uoC+vj4vL68ZM2ZgGDZnzpzQ0NDm5uaamhqofAzDdHV18/Ly2GUOx/H+/v4zZ84ICgqGhISM6G86Ojpu3rwJacePH798+fLKykocx2k02suXL6WkpDQ0NNrb20dYr11dXQYGBtzc3FxcXGvWrLl586aOjg4PD8+cOXMuXboETozw8HAJCQkuLi4RERErK6uYmBgrKythYWEhISF1dXVCwUcI1tWrV5ctW1ZVVTXircG/nz590tLSmjlzpqamZkBAQHBwcGBgoLa2tqio6LRp05KTk3Ecr6ioMDU1FRYWnjJlipCQkJaWFnyixI2ysrK2bNkyZcoUQUHBOXPmHDlyJCUlhbgF/BEbG3v48OGoqCiiDOXl5TAUk5KSmj9/vri4uLi4uISExPz58yUlJSUkJLZs2RIVFWVqaiopKSkmJiYmJiYvL6+rqxsUFHTv3r3Vq1dDoLi4uJaWFjTDnJwcHR0dERERMTExSUlJV1fX777038dP0s2XL18KCQlhGCYmJvbt2zeovvj4eD09PQMDg5UrV2IYNm/evJiYGBzHm5qaVFRUjIyMZs+eDd+cnp4eDNa6u7ttbW1BNyMiIhgMRlxcnJiYGIZh8vLyaWlpOI4/ffoUUklKSrLPGrETEhJCxCHEzsHBYcqUKaCbCQkJVVVV+/fv371799u3b9ndiOx/vHz5curUqZCVmJjYly9fIKvKykqwktrb2y0sLCCCtLQ0WEAUCqWhoYFCoaSmpiooKGAYJiIi4ufnRxSvr69vwYIFZ8+ehbLV1dVpa2uDtW5vbw9xoqOjoYXLyMiM9h5QqdTHjx+D+bxx40YQr46OjsOHD0NhVFRUurq62JP4+/tDhU+dOtXT05P9EovFSkpKgnqWlZV9+/btd2uVaDz5+fnKysoYhk2ZMuXOnTsjor179279+vWTJ0/m5eWFwQSMYZlMZlpamri4OKGb0dHR371LREQEuH3Wrl37+fNnHMfb2tpOnTq1atWq8PDw3t7e0akaGhrA8Ofj4yPqcDRJSUlSUlKgyB8+fIBAMzOz8ePHYxh29uzZEaKJ43hBQcH06dMxDNu3b19DQ8OIq6mpqRgbenp64FUoKytTUFAwMDDAv+e1vHz5MlTOrl27ampqXr16BaUSExMD46CkpGTBggXQjUVHR1OpVBKJdOXKFQzDODk5DQ0NoRLYsy0pKVFWVubh4bl79+7oB4+NjV2zZg0nJ+fatWu/fPkCvumurq7ExERRUVFBQcF3797hOE6lUkNCQoSFheFxZs2alZKSwt6xXb58mZOTE64qKiqCW4N4cfDH+fPnubi4LC0tiVS5ubnc3NxWVlbv3r178OABfNgCAgKOjo7v37/X0tISEhJKTEzMzc3dtGkT0YdlZma2tLTU19dbW1tD4MyZM3Nzc6G19vf3HzlyBMOwvXv3JiUl1dXVjdWL/QN+km4SNuDs2bNzc3Mh0NnZefv27WFhYWZmZmCyHTp0CMfxiIgIBQWFjIwM0NPv6qaQkFBcXFxHR8fWrVshjq2tLbyh7+rmCLf3j3Vz3bp19vb2GzduXL58+adPn9hzIP7GcbyxsdHCwkJAQEBUVBTDMG5ubh8fH3azFMfx4eHha9euEbo5YrDw7NmzefPmwSdy69YtIpzQTSh/cXHxtm3bMAwTFRUNDg7GcZzJZF64cAGa1oYNG6CQ7N8ElUr18/MD3dywYQMIOovFgqYF7S0rK4tIMjQ0pKamhmEY5Hnw4EF2dy2LxUpISIDHXLx4cWpq6nffMpGbg4MDFxcX3EhNTY3dE8pisVJTU2H4uWzZMhBi8KiC8a6vrw9vAcOwsLCw0Xeh0+mhoaEwMlizZk1FRUV5ebmuru7WrVujo6NHuCyIvwMDA6E1Yhi2efNmcH2OJjY2lhi+pKSkQM2YmJiAblpYWLA7DXAc7+npIaqUn58fRI2dFy9ezJgxQ0tLa9y4cVC9Dx8+ZDAYtbW1K1euNDIywr+nm1evXoVK0NbW7uvrKykpgeHalClTQkJCwAcKhvmiRYvAEsRxPDk5mZCzlpYW9pyHhoauXLkCL1dZWXlE11JbW6uhoYFh2KRJk1xcXNgvMZnMBw8erF27lugsk5KStmzZsnDhQmiza9asIUbrVVVVu3bt4uHhmTRpEoZhWlpao2s4Pz9//fr18BbKy8shMDc3V0ZGBszkgoICWVlZaJvwYbx48WLr1q3p6ekUCsXY2Bh0+dKlS0Rbe/LkCTy4goIChAwMDPj4+Kxbt87W1raxsZH4Ev5hukmMi8XExIhhwsWLF9evX5+bm+vv7w8jyjVr1rx9+1ZXV1dfX7+9vX3t2rW/ppvjx49fsmTJ6tWrFyxYoKam9uDBg/r6esj2B7pJDIh+rJvTpk2DNjZjxoygoKDRjwOZhIeHr169+sqVK1AkTk5OJSUlsCaIG/X19Z07d250eQBvb28wVYSEhNitgBG6mZOTo6SkhGHY3Llz/fz8cnNz79y5AyomKirq4eEx2qz+rm7iOB4WFkYYlY6OjsTyr8TExE2bNmloaID9u2TJEjDeief9LboJFBUVbdy4cenSpSCLkpKSL168YI+QkpKiq6vr7e2tpaUFUmJlZYXjuJ+f34IFCyIjI6Ev+bFugr2poKDg5OSkoaGxevXqly9f/lqRBgcHT5w4wc/PD6nExcVHFImA0M3Vq1d/+/YNx3EKhfJd3YT3W15eLiYmJiQkBLJ4+vTpEdNlUVFRUlJST58+3bZtG8SBHqu5uXnFihWgm6MhPkXQzS9fvoBuCgoKvnr1isVi5eTkSEtLg24SYh0YGAj1JiIiArrJZDLBGCwpKVmzZg1cnTlzZnh4OLuR6OHhATWzbt06dn8R0N3dff/+fbDrcRyPjIw0MzOzsLCANsvFxRUYGAgf0t27d3V1dZcvXw6XNDU1Rz+ajY3NhAkTwFYgXDTd3d3p6elgJ6anpy9atAjDsHnz5sGAg0QiJSUl1dbWdnZ2Hj16FHTz/PnzRNfu6uoKjyYjI4PjOJlMNjU13bZt26NHjzo6Or5bw3+Qn62bEhISxFjG19dXXV09MzMzLy8Ppkdmz56tqKgoIiLy6tUrCoUCDe+7usnDw7N3714HB4cXL14QbxQ+hR/oJlGeH+umhISErKwsiI68vHxRUdHoJ+rv7zcwMNi8eTONRqusrISmPnHixIyMDJzN3mlubjYwMIB7qaiojBjlJSQkQNc6depU9vEs6KaVlRXYBaWlpbt27cIwbPr06WpqaioqKrAOYdeuXVFRUTDcHtGR/ppuvnnzZsmSJRiGTZgwwcTEBHzzZDJZQ0PD3Nz8y5cvxGDWzMyM8NaNSTednJyUlJSSkpLs7OxAFkeoQ0pKyurVqyMiIlxdXfn4+DAM27hx48ePHy0tLbdv315WVga2zI91E9wjfHx8YHhKSEiAk+e7hIWFbd261crKCpR6woQJenp6o0fcOJtuLl++HCrt13QTx/Gurq5bt24tXLjQ0dERyjN79uz09HT2DCMiIqSlpaurqzMyMqCPxDBMVVX1+fPnW7duhXH6aIhPcevWrbBsDpRo9+7d0DEXFRWBuIiLi8fHx7NYrBcvXmzcuBHyP3PmDDwd0X/b2tru3r3b2NgYbA5dXV322+no6EDCHTt2EDYgO+3t7cQkW3h4+JkzZx4+fLhixQoMw8aNG6emptbd3T00NLR27VpnZ2eYuf2ubtbX12tqak6ZMgW+zH379o1elfHu3bsRusliseh0OswdHTlyZIRudnd3m5ubw3Opq6vn5uba2trq6OjExsZChj+ewPx9/CTdjImJgYGbiIgIIUPPnz/X1dV9+fLlwMAAGGUwEbRlyxYYRhGz7YRu9vb2Xr58GYRmhMlAKOMP/JuRkZEwp/Fj3VRTU/Pz81NXV4c2tn//fqLXIuQpPT1dREREUlLyzp07BgYG0F1zcHDY2tqyD4JaWlqOHTsGL/X48eMjRvGvX78G+05YWJiY6MRxnEwmS0tLX7x4Eeqhvr5+//798CWdPn1aVVUVwzBOTs59+/bBp8NuSgO/pptPnjwBR7OQkJCbmxukSkhImDJlypUrV7q6uk6fPg1TLvLy8sSUzq/pJnHHnp4eQmR37Njh7OyM4zgxc7Vo0aKKigoiSUpKipqaWlpa2rdv38COnjNnjqqq6vr164ODgzs6OsCX92PdhAoXERFZsmQJ/L18+XLCz8veTQ4ODu7atUtfX7+vr+/p06eTJ0/GMGzBggXp6emEt5rInH2cDoPEH4zT8/LyVFRUQkJCBgcHN2zYAGV+/Pgxe+VERkbOnTsXHt/FxYVYeLdmzRp4m6MfEMdxBwcHKOfcuXO1tLT27Nmjra195cqVvLw8osJBtgQFBffs2XPq1CloLKtXr753715tbS27Y6qsrExDQyMwMPDz58/gmpw3b15OTg7xyrZv3w6l0tXV/Y8GWlRU1KlTp1JSUpycnCDV1KlTCwoKnj9/vmrVqvfv3xMToYRuEjV89+5dbW3ty5cvr1u3DsMwMTGxkJCQEXFG6ybBd3Wzvr4eOnsuLq7FixcrKiqCUQVOc2JW8M/lJ+lmQkICWBZiYmJ1dXUQCPZmYmIijuOpqakwxzpt2jToKJhM5mjdrK2thToSFBQk1t/g/7/78td0s6OjQ15e/vjx4/h/0s3169dnZ2e/ePECZkLGjx9/9epVWPMIt2AymdbW1gICAvr6+qampsuWLSNmgefNm8c+XdvV1QWdIYxGRyycTE1NheVZS5YsIbxU8Jji4uL+/v7wyisrK3fv3o1h2LJly/Lz89PS0ubMmQOabmFhQXwf/1E3mUwmWOsYhsnJyRUWFkLko0eP8vDw7Nu3z8HB4dChQ+CjmDp16s2bN4nq/TXdpNPphYWFT548AYlPSEiYNGmSurq6o6Ojuro6yMSkSZNsbGyIJCkpKcR7h0kzGMDKyMh0dHT09/f/lnE6mJnKysoBAQE7d+4kzCXCk0vURkpKioCAwPbt21++fGlpaQn998SJEy9cuEB8P729vdClEbq5cOHCH/s3h4aG3NzcZs+e7e/vHxkZSfji9+/fD184FCAiIkJKSgp8U3Q63crKipg24ebmHjH/RkDo5qZNm+7evRsTEwPrSYg6/PLlCwzRREVFNTQ0oO1wcnIePHiQPRr8cfv27b179+bk5BQUFMC8yoQJE06fPk304uA9xzDMyMgIhiB9fX1xcXF37txxd3d/8OCBm5ubn58fuMLc3d23bdtWVlaWlZUFheTm5j537tzatWutra2JFS+jdbO3t1dNTc3Ly4vJZF66dIlo2iNK+117E652d3ePHqc3NTXp6emB1cJet87OztDc/sG6mZycDAONuXPnEut+bty4oaKiArOW7e3tYN5v3LgRxI5Op8vLy0MtGBsbw9rG4uJi6GZhXui794qLi4NU0tLS7OHe3t58fHwXL17EcTwmJgbiLFiwgKjWW7duEbMNBQUFdDrdxcUFxlYjppi/fv26efNmAwMD2DNTVlaWnJwsKSkJ9rKbmxv7CNfe3h5089y5cyOKWltbC129nJwczFcCz58/FxcXJ0IyMzPBvQViNzQ05OzsDD5+DMOePHlC3IvIgUaj+fv7g24qKSmB5djc3Lxv3z5oYKamptBhlJWVycvLHzly5NatWzdv3nRzc9u/fz/IhIqKCjEtS8yny8jIsC9g7OrqsrCwOHr0KIzjNm3aJCkpuWPHjiNHjly5cgXmmjAMW7FiBWGGp6WlKSsrw7Daz88Panjy5MmOjo44jg8MDMydO/c36uaaNWuKiopCQkLA5OTi4jIwMIDvh7AlDQwMlixZYmFh4eLiYm5uDnKDYdi6devAtioqKrKzs7t69Wpzc/Pr169hnlpGRgZcLr+mmyUlJUpKStLS0oaGhvr6+lu2bAHLYOLEif7+/kRTDwsLk5eXJwS6srJSR0cH3t28efPCw8O/+w0TXfh3DVImk5mYmAi1JCsrm5ycTAwjREVFR7SLrq6uvXv3ysnJ3blz59atWzAnA30wMZ9z6NAh6Lq0tbVBoDs6OhwdHaF7BnR0dOArcnBwkJeXr6ioaGhogKEP7DGZMWMG9IVnz54doZtASEjIjBkzzMzMHj16RCj12rVrCUMKyMzMXLx4MWjFCHuzp6fnB7rJw8OjqqpqZGQEUjN//vyIiAh2c+dP5C/XTRqNVlpaamlpCdU0fvx4d3f30tLS0tJSXV1dcXFxBwcH6MciIyNnzpx57949HMc7OzsjIyOhbWAYtn79+qioqIKCAh8fn5kzZ0LguXPnsrKy2CdGqVRqZWUlsSiBj48vJCQkJiYmJibGzc0N2oOTk1N9fb2NjQ3EERAQyM7OJpPJsEAdhG/hwoXPnj0bHh6urKxUVFQkejB/f/+6urqqqipTU1NxcfF79+4RPXZtbS2hEXJycgkJCcPDwwwGo6qqChZDYBimq6tLIpGoVCrxFvv6+k6cOAFCdurUqfb29u7u7tLSUjMzMz09PZheZDKZ/v7+YANKSEgkJCTgOE6hUAgja/369a9fvx5hybJYLB8fH2jtK1eurKqqotPp7u7ukM/27ds/fvwI+VhYWCxduhTmQIAXL15AgxEWFvbx8YHAly9fgr0pJSVFuPD6+/vDwsLmzZt34sQJBoPx6dOnpUuXwow/kJ6eDmo7Y8aMiIgICExKSjpw4AD0lw0NDbq6uhiGrV69GoYUfX19hL1JuKhGEB0dTcxjlJWVkclkc3NzmMOdOXMmMVLGcbysrExOTu7Ro0fsaQmlDg0NZTAYMCDAMCw+Pv7NmzcwbyYvLw+fJY1GMzU1hamM06dPg3UPlSkrKxsaGpqZmZmVlfXu3TstLS1osceOHSPWeMXExBCTvEBVVRXIjaio6LNnz777gMR8+t69e2tqakZcZTKZr1+/hlpatGhRenp6X18fLEqBkJKSEiKyn5+fqqqqoaGhg4PD1atXjY2NYajOx8f39OlT+BSDg4OhWW3cuJEYLdFotHv37oHTZsmSJYR7LTAwUFdX99OnT4ODgx4eHhABwzBjY2NwVp45c2a0bra3tysqKi5YsGDt2rWrVq1av3491PPs2bO9vb3Zny4tLQ0c3JKSkiP6gBH2JlQyoZv8/LTnWYAAACAASURBVPyXLl2qqamBZcjQN8D05ojlNH+cv1A3oZT9/f0eHh7Lli1TUFBYunSpvLz8ypUrYWv55s2b5eXl169fHx8fj+N4SUmJj49PbW0tbJc0MTFZvny5goKCgoLC2rVrjxw5Ymdnd+jQIXl5echq06ZNVlZW7OOX3t7ex48fq6qqKvyCrKysjIyMjIyMrKysnJzcvn37nj9/7uvru2LFCmlpaUlJSRkZGVNT08+fP7u6ui5atEhERERERERUVNTAwKC2tra6unr37t0QOHv2bBkZGRcXF3t7+yVLlsyZM0dfXx8+suHh4efPn+/YsUNUVFRERGTWrFmGhoZ1dXU9PT2enp4bN26EPBUVFd3c3Kqrq9kHDikpKVu3bp09e/aiRYuuXr3q7u5+8eJFdXV14vMtKioyMTERFhbm4eGZOnWqmZkZNKTU1FRpaWlubu7x48dv3rw5MzOT2IBBo9HKysqsrKwmTZrEw8MjLS0dFxcXExOzatUqMTGxffv2wZZW2EApJSW1fv365ORkGAcMDw/7+vqC8QKa++nTp69fv1pbW4MK8/LyOjk5ZWVlJSUl2djYzJkzh4uL6/bt27m5ubt27ZKTk4uKiiL2L6SmphKTFcuWLcvKyiotLT1x4oSYmJi7uzuYe3fv3p04cSKM13p7e58/f070l87Ozm1tbbBHCx6NyWQ2Nzc7OjpCYWARPovF+vjxIzFShqU5ra2tdXV1ZmZmUlJSkZGRRJ1//vx5y5YtRJGKioru3bsH483Y2FgPDw8woGBJHI7jJBIJFs+CILa0tDCZzPT0dEVFxRGzK2FhYbA1YOHChWAo0en0Bw8eSElJwVIY4imePn06Z84c8DV9t+0Q6ze1tLSItOzNPjk5GTqk+fPngz8hJycH5lE5ODg0NDRAwgYGBtTU1BwcHIgBUF9fn4ODA3TVurq6ID3t7e16enrjx4+fPHky+KaB0NBQ6I3WrVtXXFxMBB48eBBktLm5GRbqcnNzE30A4QtiX4eUkJAgIyPDvubByckJNHf79u3sO7uCg4Ohh964cSOxZpEovL6+PujmhQsXYATT0tICU698fHwXLlzAcby4uFhOTg4saC0tLdhrgH9vd+nv5q/VTVgGMTw8DHtaqVQq7G+lUqlUKhV2uVIoFBqNxvwFHMeZTCadTh/+BUgF5zgMDQ1BCCQEm46oDiaTSaPRiL2xsLOCOOthaGiITqeTyeTs7Oy0tLTKysrCwsLS0tJXr15VV1enpqZGR0fHx8fHx8dHR0e/fPmyubm5vb09Li4uNjY2Pj4+Li4uOjr6+fPnoEGxsbGRkZHgIhwcHPz48WN8fHxsbCxcjYyMbGpq6ujoSElJiYmJiY+PT0hIePLkia2tLWx7J+qHxWK1tbVFRkaeO3fO2NjYwsLi8ePH1dXVxAsOCgo6evToiV8wNDS8ceMGPLWHh4eJiYmxsbG+vv7jx4+JHdBwFomZmdnx48ch1alTp44fP25nZ5eamkr4fKurq7dv33748GFtbW1DQ8PS0lIcx+vr601NTSUkJMTFxWVkZHbv3n3o0KHjx4/LyclBoLy8vJKS0tKlSyUlJefOnSsmJrZp06a0tDRra+sFCxbAPAa0MdDuJUuWwPYPKSkpbW3tkydPLl26VEJCYseOHTCsy8/PP336dEhICIvFevv2rbq6+vTp00VFRUVFRZWVldmfC6r6yZMny5cvnzp16tSpU4WEhMCnVlVVtW/fPsFfUFRUvHPnzqVLl+bNmzd79uyLFy+CMUuj0RITEzdv3jx16lRBQcFZs2Y5OTnBrrAFCxbY29vv379fQEBAXV0ddkxRKBQfH5+lS5fCvbZu3RoXF5eTk2NgYCAkJKStrQ1mO8T09vYWERGBswjU1dUrKiqKi4tVVFSmTJliZ2fX29tLzFGwWCwHB4eFCxeGhoaObjUkEklfX5+HhwfyycnJgU1TxEdOIpFu3749c+bM8ePHCwoKOjs7Qw/09OlTmIjj5OS8fv16cXHxlStXBAUFb968Sbz04eFhLy8v7BeCg4NBfcrLyw8cOMDPzy8nJxcXF0cikerq6pycnGAEtnnzZhikd3Z2Ghsbi4iIJCQkDAwM0Gi0J0+e8PHxqamp1dfXk8nklpYWQ0NDyHzTpk1wllh5ebmJicmRI0cICcNxPDo6GvY4CAoK3r17F0pIJpMtLCzAB62hofH582f24wsaGxuJvVsnT55sbm5mMBjV1dUwZAHvE7hEgoKCiOW6lpaWnZ2dRM3/AUn7f/y1uvnbbWP2aGN9trHGhx3r7P9lMBig3fBlwykGoE3wBzwIg8EAyYZLNBoNTCH4m0gCuTEYDPiD2CBPo9H6+/tHzGXB3wwGA87TIyYoiAhkMrm3t5f8CxCH9csO3IGBAdiiSyaTCZsCDg2CY4fgcKCenp7u7m446IjIHE6XgDOHurq6wIFAp9NhF3BnZ2d3dzecy9fZ2dnW1tb1Cx0dHa2trS0tLSQSqaOjo7e3l0aj9fT0tLe3t7e3d3R0QFYQCFl1dnbCQRWwXxgC4cgiOMeISqUyGIzKysrQ0NDg4OBv377V19fHxsZmZGSwGyODg4MZGRnBwcFBQUEhISFPnjxJSkrq7u6GPfsQGBQUFBQUFBERERYWBn+HhISAkd7R0ZGamhoaGhoSEgL7CKOjo/v7+9vb2z09PY2MjAwMDPz8/EgkEtyORCKdPn362rVrQUFBYWFh586ds7S0dHR0PHXqlK6uro6OjqOjI1RpUVERsWf8wIED2trafn5+MTExOjo6+/btO3XqVF5eHrHrDMfx7u7u0NBQMBXZoVKpN27cgM3psP3cxsYmMzOTiEChUO7evbtu3TpYJLBhwwYJCQkPDw8cx3t6eq5duyYgIDBlypTZs2fPmzdv1qxZgoKCCgoKoaGhIByFhYVKSkrQu0yZMmXZsmVRUVGgTY2NjdeuXZs3b56cnJypqamenp6CgsLUqVPXrFnj4eEBzkRvb28pKSlBQcFdu3aBy6ihoWHTpk3Pnj2D7V7Hjh2TkJDg5eXl4+ObP3++o6Pj27dv9fT0hISE1q5dGxMTA593e3v7rVu3ICYvL6+0tHRiYiKdTodTFCBwxYoVjo6OhM+BQqEEBgbKycnBVSUlpZCQkM+fPz99+lRVVZWXl3fixInEcQf19fWLFy+GPmzy5MmGhobFxcV/4gmQ6NxixH8RDAaD/QQdOp3O7g7Gf5F7GE/Q6XQYVbB3Y3Q6HVLBUXUQCGfNQYYwTIG0NBqNQqFA/hQKBQ4ZYvcU0+l0EonU398POXd3d7e2toLuQ+dBTBNRKBQ4IhY6CRKJBGe8EqcWsXdaAAykRtQAi8VqbW1tbW0l8mltbWVfagr2ZnV1NZx/0dzcXF5eTiKRQBYHBgaqq6vh4MGvX7+Wl5fX1NRUV1cTS8QHBwchQk1NTW1tbVVVFftJTv39/d++fXv//r2np2dAQMD79++rqqrgYCToxdva2qqrq4uLizMzM2FUxGQyW1paYJqhsbExPDz8/v377u7uUVFRiYmJUVFRxcXFjx49unfvnre3d3JyMtiV9fX1UVFRnp6enp6eHh4eDx48+Pjx49DQ0MuXL728vCDc19f30aNHxNKr3t7esLAwuOTl5XXr1i0XF5enT5/6+fnduXPHy8vLy8vLzc0tKCiIQqGUlpYaGRmZmZnduHHjyJEj27Ztu3PnDix9/VNAuolA/C/wR5x3hIuMoLe3d/S+gBH5sx9/RxRgaGiITCYTh58ODAwMDQ3Boa5kMnlgYACGX8PDwxAILjgAzhSHJJBPd3c3IdkwEiKTyXC1p6cHDk+C2VTIoaenp62tjcFgkMnkpqYmOEiJRCLBibFDQ0P/gHE6AoH4K2D9Bv5jWvYQQnNHpx0Rc0Ty33jTP8hfmvnvA+kmAoFAjA2kmwgEAjE2kG4iEAjE2EC6iUAgEGMD6SYCgUCMDaSbCAQCMTaQbiIQCMTYQLqJQCAQYwPpJgKBQIwNpJsIBAIxNpBuIhAIxNhAuolAIBBjA+kmAoFAjA2kmwgEAjE2kG4iEAjE2EC6iUAgEGMD6SYCgUCMDaSbCAQCMTaQbiIQCMTYQLqJQCAQYwPpJuL7UCiU/v7+gYEB4ld54Qe8mEwmlUqFn9gd/RtexG/QUyiUET/h+2sQ2f72so3O9rs/FvbbM0QgxgTSTcRIhoeHs7Ozb926dfz4cUtLy6CgoMHBQeJqU1PT3bt3z549+/HjxxEJid9ETE9PNzc3j4mJ+Y137OjoKCgoaGlpgR+JHR2BxWIxGAz40XMGg/FruslkMjs7Oz99+tTa2jomIUYgxgTSTQSOs9lrJBLJ3Nx89erVdnZ27u7ujo6Oe/fu1dTUzMjIgJiZmZkrV64UFhYODg4m0rJn1dzcrK2tzcvL6+DggI+y/r5rDDY0NJw9e3bJkiUrV640MzPr7u4eEfP169crV65cu3atubl5eno6g8EYXX4cxzMyMpYsWbJ+/frk5GSkm4i/DqSbiP9HS0vLyZMnJ02aZGpq+u3bt97eXhKJ9OrVqwULFsjKyn769AnH8Y6Ojj179owbN87f3x//3m9bk8lkHR0dDMMuXLhABI7QTeIHuyFkaGgoPj5eQkICw7ApU6Z8/vyZPVVjY6OhoSGGYZMmTbp//35TU9N37U0cxysqKpSUlCZNmhQVFYXG6Yi/DqSbiP+Ho6PjxIkTVVVVW1pa2MMvX76MYZimpmZdXR2O46dOnRo/fvyTJ09+LR9nZ2cODo6LFy/+lpuCwNXV1W3ZsgXDME5OTmdn576+PhzHwWYMCwsTEBDAMExaWjo9Pf0HWfX19Z0/f15YWDguLu633BqB+H0g3UT8XxoaGtatW4dh2LVr10ZcKi8vFxER4eTkTEhIwHHc0NBwwoQJYG8ODQ09ePDg8OHDR48etbe3J5FIOI77+vry8PAcPXo0ICDAxMTk5s2bDQ0NOI5TqdSHDx/a2tpWVVURmYNufv36ddeuXVJSUhiGrVixAuKzWKympiYLCwshISE+Pr6VK1fW19c3NzeHhISEhoaWlZX19fUlJyf7+vpmZGRQKJSenh4LCwsREZFnz54lJyc/ffo0JCQkMTGxo6MDx/Hi4uL79++/efMGx/GBgYGEhAQfH5+QkJD6+nooSUtLy+vXr3Nzcz98+PDs2bPy8nKikGQyOSYm5sGDBxkZGVQqFf/e3BTi3wPSTcT/5ePHj3Jycvz8/AEBASMciENDQ/PmzcMw7Pbt2zU1Nbt27Zo4cWJoaGh3d7e7u/u2bdtsbGyMjY15eXkNDAxaW1sDAgImT568fv36M2fOiIiIcHBwXLlyBfJRVlbGMCw5OZnIHATo8+fPBw8e1NPTExMTmzhxYlhY2PDwMI7jjx8/3rZt2/79+4WEhFRUVHAcr62t3bZtm7i4uLe3d29v77Vr16ZNm2ZgYNDS0kImk0E3w8PDQ0JCli1bNnv27NOnTzc2NuI47ufnJyMj4+/v39LScvr0aSUlpSNHjigoKOzfv7+srKympubMmTMKCgqqqqq7d+9esGCBjo5OVlYWnU6vqamxtrbet2/fli1blJWV7927RyKRkG7+m0G6ifi/5OTkyMvLCwsLv3jxYsSlgYGBuXPnYhh2//79r1+/qqur8/HxJSQk5OfnCwsLy8jIPHz48MaNGxiGYRj29u3b8PBwXl7ePXv2fP361c3NDcOwpUuXMhgMJpMZEhJy/fr1mpqaEbf4/Pmztra2ubn5+fPn+fj4Nm7cWF9f39/fr6mpqa+vf//+fR4eHiUlJRzHBwcHjx8/Pm7cuKtXrzIYjPDw8MmTJ6uoqNTX1w8ODlpaWs6cOTMxMZFEImlqamIYdu7cud7eXhzHL126pKmp2djYmJqaimHYzp078/Ly1NTUMAxzc3P7+vXrxo0bMQxTVFR0dHQEF+3Zs2f7+/tdXV0xDHNxcYmPjxcVFZ0zZ87Lly9/yjtB/Jfyr9ZNEomUmJgIdg2isLBw2bJlkydPfvr06YhL3d3dMGnz9u1bHMe1tbX5+flDQkJ8fX25ubnXrVunoqKiqqqqoaGho6NTVlb29OlTTk5OW1tbHMdjY2MxDFu0aNGP67mkpERNTc3Y2DgrK2vhwoUYhmVkZCQkJCxfvjw+Pv7Zs2cYhikrK+M4TqfTPTw8BAUFr169Ojw8XFhYKCcnp6Ki0tDQQOjmixcvmExmWlqamJiYoqJiTU1NU1PTzp07r169iuN4WVmZpaXl/fv3Y2JiNm/ezMnJee7cORzHzc3NOTk5wf+QlpbGyclpamra19cXGRl5+vTp9PR0Pz+/uXPnTp06lVhLgPgBQ0NDsDTif49/tW5++vTJyMgIjBEEiUTavHkzhmE3b97E/3//XV5enrCwsICAQG5uLpPJ1NTUFBQU9PDwuHjxorCwMPs6TTKZTKPRbt26xcHBAboZFRWFYdjixYvBLfhrfP78eefOnefPn+/q6jIzMxs3bpylpeXu3buNjY07OjqePHlC6CaTyfTz8xMSEgLdzM3NXbRo0aZNm9h1MzY2FrLds2cPhmGPHj26e/eulpbWhw8foJBZWVnm5uZ79+4VFRUdN24cuBFOnDjBw8MTGhqK43hSUhInJ6eJicnQ0BCNRnv79q21tbWysvKMGTNmzZo1umtBjKarq6uiouJ/0qHx79VNWBDz3UXU/1qcnJy4ubn37t1LJpOJwOHh4bNnz06cONHExKS5uZlGo+3fv3/ixIlJSUkvXryAAW99fT2VSm1tbbW2tq6oqDAxMcEwDMQI7M3FixfT6XQcx6lU6tDQ0OjFlSUlJYcPHw4KCqLT6RkZGWDe8vPzR0RE4DgeGhqKYRj4N4eHhx0cHCZPngz6HhAQwMvLq6am1tzcTKFQzpw5M3PmTGI+/dGjRzNmzFi/fv2yZctcXV1xHGcwGBEREVJSUnv27Kmqqrpy5QofH9/Dhw9xHDcxMSF089WrV5ycnCdPnuzt7X348OGcOXMMDAzKy8t1dXX5+fnDw8P/+rfxj2fEgrP/Jf7Vuvl3F+G/CKiN4eHhEydOTJ8+3dXVtbm5ubOzk0QixcbGzpo1S1FRsbKyksViFRYWrlixgouLKzw8PDc3d+bMmRiGKSkpubi4HDhwQEFBITc3V09PD8MwGxsbOp0eHByMYZikpCTIZVBQkJubGzGFTZCdna2pqRkcHEyn05lMpoaGBoZhe/bsAU/o48ePMQxbs2bN8PDw4OCgtbU1Nze3ra1tW1ubk5MTJyenoqJiWVlZf3//iRMnZsyYQZjAHR0d+/btwzBs5cqVYGx2dXWZm5sLCAgEBQU1NjYeOnQIw7DIyMjh4WE9Pb3x48eHhITgOB4TE4NhmLm5eWNjo4SEhLCwcG5ubmlp6YoVK/j5+f39/Yntp387LDb+7rJ8h//OUv1B/r26ifgufX19N2/elJOT27x588mTJ/fv3y8lJWVqagorN3Ecj4mJkZOT4+Pjs7GxoVAoERERIiIi3NzcgoKCCxcujI+Pz8/PV1ZWnjBhwokTJ8rLy21tbSdMmCAlJfX58+e+vr7ly5dPmzYN/KQEw8PDbm5ukyZNUlNTy8zMZLFYoaGhS5cu9fLyYjKZPT09Z86c4ebmnj9/fkREBJPJTElJERcXX7JkiaGhoby8/IQJE2bMmAErh5YtWzZ16lQPDw8KhQKZ+/r6Tpo0ydjYGNaEdnd329ra8vLybt++/fDhw9OnT+fg4NixY0dSUpK2tjaGYZ6enmQy2dbWFsOwAwcOVFVVzZ8/n5+f/+7du46OjnPmzOHn5z958mRJScnPfTO/CvsOgr+3JP8ekG4iRkImkz9+/Ojn5+fu7u7v719YWNjV1UVcLSgoyMnJSUpKioiI6O/vp9PpRUVFrq6uLi4uxcXFDAbj69evfn5+Li4uEREReXl5cXFxrq6u3t7e+fn5g4ODsbGxAQEBzc3N7Hesqam5ffu2qanpnj17vLy8BgYGKBQKzKdTqdSYmBg7OztfX98LFy5cuHCBwWBQqdS4uLgDBw6YmZkFBgba2dndunWru7s7Jydn27ZtW7duNTU1LSgogMyjo6PV1NQiIyPhv0wms6Cg4MCBAxoaGsePHz9z5oyWlpaFhYW3t7epqamSkpK9vX1iYuKFCxdUVVWPHj0aFxfn7e2tqqq6bt06Jyen06dPb9iwwc7ObvSSgL8L4mAUpJs/DaSbiP8Pou0NDQ319PSwn+iB/7InEv4eGBggpnoGBweJmBQKZeAX+vv7yWQymUweHBwcGBiA5s3uU4bR5eDgYHNzc3t7e1VVVVNTE3hCAQaD0dLS0tjYODw83NHRUVtbC2kZDEZ9fX1DQwOVSu3u7u7v78dxvK+vr6KioqqqqrKyEkJwHDcyMrKysmpvb2fPs7GxsaqqqqGhobOzE9bSt7S01NXVVVVV1dXVtba2NjQ0VFdXV1dXk0gkMplcVVWVn5/f0tLS1tZWUVHR1NT042mun0xzc3Ntbe3fXYp/EUg3Ef+b+Pn5aWhoqKqqiomJ/c9P45DJZPBCIH4OSDcR/4MMDg7a29vDutE7d+6wG5sIxB8H6SbifxAmk1lRUREcHJydnf1fNaBG/G+AdBOBQCDGBtJNBAKBGBtINxEIBGJsIN1EIBCIsYF0E4FAIMYG0k0EAoEYG0g3EQgEYmwg3UQgEIixgXQTgUAgxgbSTQQCgRgbSDcRCARibCDdRCAQiLGBdBOBQCDGxj9PN9Gh1ggE4u/lL9HNET8RRZwQ/ifmiSMBRSAQfxN/pm4ODw+XlJS0trbCDyFUV1dnZ2fHxcXl5ub+8cxBN/v7+0tKSrKysoqKiv57flAQgUD8q/gzdTMxMVFGRsbDwwMMTCsrq3Hjxv3HXykYHBxsb28fHh7+LbfIzs5esWIFBweHqqrqiJ++QSAQiJ/Dn6abX7582bp1Kzc3t7u7O4jgnTt3uLi4Vq9enZ2dTURjMBg9PT1kMplOp7NYLDKZ7OLiYmFhUVFRgeM4nU6n0+kMBoOIT6fTaTQag8GAwJycHFlZWR4eHnt7+8HBQRqNhn7JD4FA/GT+HN0sKyvT0NAYN27chAkTvLy8QDctLCwwDFNXV4+MjPz48SOTyRwaGnr58qWFhYWLi8ubN28+ffpkY2MzceLE7du3FxQUFBUVhYeHh4WFxcbG1tbW0un0pqamxMTE8PDwiIiIxMTErq6ugoKChQsXLliwICUlJSoqKiYmpru7+095BAQCgfiN/H7dJCZqKisrL168uGHDBgzDuLm5fXx8qFQqiUTavHkzhmGTJk2aM2eOqqoqKJ2srOzhw4ePHDmioaFhZGQ0f/58DMMOHTp08eLFxYsXCwsLT58+XUxMzNLSMiYmRltbW1NTU1VVdebMmQoKCunp6YmJidzc3Dt27EhPT5eVlT1+/HhpaSkyNhEIxM/kd+om/NQ9juPd3d1OTk4WFhZJSUmcnJzjxo3z8fGh0WixsbGioqILFiy4cOGCiooKLy+vvb29k5MTJyfn4cOHU1JSwsPDb9++LSoqKi8v//HjRy8vLwzDMAzj4+PbtGmTk5PT5s2b582bFxMTc/bsWQzD1q1bl5aWZmdnx8nJqaqqam1t7eDgUFRUNDAw8KdWCAKBQPwHfr9u4jg+MDBw/fp1fn7+6dOnb9iwgYODg5ub29fXl8FgXLlyZdy4cUePHv3y5YuJiQkfH5+rq2tsbCyYnz4+PmQy2c7ObuLEiQYGBgwGw8fHB8MwCQmJkJCQgoKC69evCwgIHD9+vKOj4/jx4xiGXblypaioSFFRkYODY/LkyTIyMmVlZX9qVSAQCMRvYsy6SQzPWSyWm5vbzp0779279+DBA7AKx48f7+vr29fXp6mpiWGYp6dnfn6+hITEokWL3r17l5WVZWhoiGGYqKhoZmbmli1bxo8f//Tp0/7+/qNHj2IYpqOjg+P40NCQmpoaNzd3fHx8fHy8uLi4kJDQmzdvPnz4wMfHN27cuIkTJ06fPp2YbkLjdAQC8TP5nbpJJpN9fX03btzo6ekJ4WlpaTDQfvjwYVZWlqSkpKCgYHh4+MWLFzEMO3nypK+v76lTp1JTU3l5eTk5Od3c3JYsWYJhmI+Pz7Nnz0RERPj5+T08PHAcb21tlZeXxzDM29t7x44dGIbNnj373r17J0+exDBs1apVurq6nJycysrKgYGB/f39f3KVIBAIxA/5PbqJ43h2draKioqSklJWVhaO43V1dYcPH54xY4aYmNitW7fevHmza9eupUuXnjhxQlNT8/Tp07m5uXZ2dosWLbK3t5eVlbW1tU1JSdm8ebOwsLCvr6+7u7uwsPC2bds+f/6M43hPT4+xsbGEhMSJEydUVVVFRERWrVplZ2e3b98+SUlJd3f38PBwYWFhUVFRb29vpJsIBOIn8zv9m4WFhQ8fPgwICAAnY319/d27d728vHx9fRMSEkgkUmZmpre3961bt6KiomDqJjc318PD4+bNmwEBAT09PcPDwzExMb6+viQSqba21sPDIykpiU6n4zhOp9M/ffrk7+8fGxv7+vXrJ0+eRERElJeXp6enh4aG1tfXf/v27eHDh3FxcVAYNE5HIBA/k3/euR4IBAGLxSopKamrq/u7C4L4d4F0E/HPxsfH59WrV393KRD/Lv6RuklM6I8I+XESIs7oo5UQ/1BYLBaDwYClxAjET+Ofqpu/Jny/JRxaGpJOBALx+/in6iaTyaRSqRQKhUwmDw4ODgwMUCiUH9gdLBaLTqe3tLRUVVXBlvb/Vd2EJ/21Q/aYTCaNRoP5NwQC8fv4R+omjuM0Gi0+Pn7t2rWrVq06fvy4hoaGvr7+27dvQS++q4kJCQlr167V09Orra396eXF8VGOhR8IN+sXRvz3x4Y2XKqpqbG1tb1169Z3j+bLzc01Nzd/9OjRH3qS3wWVSi0pKfn06dN/2wGA7BX7x/0586R0IgAAIABJREFUI1L9iU6h0Tn/Kdn+dfxF9fAXMabi/fN0E4xNFov15cuXyZMnq6iovH79Oj093dTUdPXq1ZGRkb+WMCMjY9asWVpaWn9Xu2U3h/+jbo6wnfPy8q5cuUIsvfpuEvjjxYsX/Pz8RkZG39XNp0+fioiIWFlZjbn0fwwqlRoREbFu3bpr16719PT85Lv/mBFaSYT/bmdOW1tbYGDgjRs32E9Q/FNgMpmNjY0JCQl5eXkUCuXPzfzPZcQ3/N+pm7+7SP883cR/mQ148+aNsLCwi4sLBH748EFaWlpNTa2+vv67qV6+fCklJXX58uWfWNKRNDc3nz9//t27d78lMpPJPHfuXHx8PI7jlZWVXl5eycnJ/zFVWFgYLy/vw4cP2Y8xJbhx44a4uPjz58/HWvI/CIPBCAgI4OXl9ff3/287qB8aD51O7+npodFoXV1dzs7O9vb2v7tRDQ8PGxoaKigovH///k8tKY7jeGFh4bp16+7cufOPONGmr6/P29vb39+fTCb/3WX5Po2NjdnZ2S0tLWNK9Y/UTRzHe3p6rKysZGRkMjMzIeTbt29KSkpLliwpLS3FcTwtLe3kyZM2Njampqbe3t5kMvnq1asLFy6MiIjAcbyrq8vHx+fcuXOnTp26ceNGT09PSkrKqVOngoOD3d3db9++XVpa+uHDh5s3b75582a0MfLy5cujR4+amZkVFBRQqdTExMSwsLCuri4cx9++fZuXlwe2XmFh4YMHDzw8PEJCQkpKSjo6OmB7/oULF2pra58/f56fnw/PUlNTM8IKbmpqunHjBoZh165d6+3tDQsLi4mJGRgYaG5u/vDhQ1lZWW9vb1RUVGFhITgrGQxGZmZmQkLChQsXFixY0NraiuM4jUbLzMxMSUkpLi5ubW1lsVgnT55cvnx5eXl5cXHx169f2bV1aGiopqams7NzaGiooqICcgCoVGppaWlJSQmVSsVxvKOjo6GhgcFgsDtSKyoqRlhAw8PDREhPT4+1tbWYmNjvWGv5c+wUNzc3Hx+foaEhFosVExNz//7933jf0dHq6+vXrFmzc+dOonLG9Ajp6ekjzEkiOZPJjIqK4uPji4qKYr/KvsKEQqE8e/asr69vRAQik/b29uzs7BFlG+EIGh34XUZnzv5fEol06dKl/fv3v3nzBr6cEWm7u7vBacZisahU6sDAAHyQozP/tbuPuOlYwXE8IyPD1tb2N5oyBP9U3WxpaVFUVNy0aRNhXdbU1CgrK69evfrdu3f+/v6ampqWlpa6uroYhp06daq5uVlNTW379u0kEqmpqcnOzk5PT+/y5csiIiKioqL19fX+/v4YhikoKGzbtm3u3Lk7duzQ0tKSlpa2sbEhhhtQ0a9fv96xY4eysvL8+fMPHTr09u1bOTm55cuXV1ZW1tfXq6qqgvcwMjLS3Nzc3t5eXV1dSkoK9lZNnjxZVlY2KCjI09NzyZIlZ8+e7ezs9PX1NTMza2xsZH/AjIwMCQmJadOmRUVFvXjxQlpa2tLSEsfxqKgoVVVVW1tba2vrZcuWmZiYNDc3MxiM+/fvGxsbm5qazp07V1dXF8fxgYEBOzu7M2fOHD16VFlZOSwsrKmpSU9P79ChQ0FBQRoaGn5+fuymX0VFhaWlpZaWlrm5ubGxsZ6eHqyLLCsrc3R0PHnypIaGRkRERHZ2trm5ubW1ta+vr5WVVWRk5KdPny5fvnzs2LETJ058/PgRx3EymRwVFXXmzBlTU1N7e/uMjIzKykpZWVktLa2AgAB7e/ubN292dna2t7ffv3//3Llz58+fv3//fn5+fnR09LVr17y9va2srCwtLRMTE6EH+vLli7W19blz51xdXW/fvt3e3v7w4cPHjx/39PSkpqZeunQJ9vv+GsnJyRcvXnRxccnMzISNubm5ubdu3Xr06FFJSQmDwQgODhYSEtq2bVtubu779++Tk5O/ffsGaUtLS588eRIXF5ecnNzV1VVRUZGQkFBQUJCenv706dOqqqrRt4uOjpaRkTE2Ns7MzCwoKCA6p87OzqioqDdv3oAmtra2tra20mg0Mpnc3NzMYrFoNFpMTMzq1asfPHgA1djc3Eyj0VgsFvw+wsDAwI0bN1atWlVRUUEikaqrq8lkMruItLW1eXl5HTx4EHRzaGgIegKibJWVlba2tuyjLtava/oPLv0gCbSXnp6e69evKyoqpqSkEFfZR+40Gi0wMNDNzQ3H8eHhYU9Pz3fv3oG8/pjfuOxsdLTvJqyvr1dXV/fx8fkteRL8U3UzJydHVFTUxMSko6MDQj58+CAhIaGpqRkYGCgrK3v58mUqlRoSEiIiIvLq1auMjIx58+Y5ODjQ6XQHB4eNGzdmZmZ2dXWpqant2rWrtbX1xo0bfHx8RkZGZ86cmTx58vr16y0sLBQUFBwdHUfc+v79+7Nmzbp69Wp0dPT9+/dfvHgxY8YMKSmppqamiIgICQmJlJSUd+/erV271t7evqGhQV9fX1BQ8NWrVwUFBdOmTbty5UpnZ6e7uzuGYWfOnPn06dOaNWuUlZXBXAWYTGZAQMCkSZOsrKxIJNLDhw8FBATAKeni4oJhmIyMzKlTp1atWqWurv7lyxdPT89NmzYFBwdfvXqVm5s7ODi4vb39+vXroHRGRkZcXFwBAQGvXr3avHnz/v37LS0tra2tP378yN4w8vLyJCUlp06damNjc+3aNeg8GhoaTp8+bWhoaG1tzcnJeerUqaCgoLlz5/Ly8q5cuXLbtm0mJia7d+8+cuTI9evXx48ff/v27e7ubldX10OHDtnb2ysrK8NRL6mpqXPmzPH09Ny/f//evXuvXbuWnJx87ty53bt3nzx5UkRERFxcPCkpycTEBMMwTU3NY8eOycjI7Ny5s7y8PC8vz9jY+ODBg9u3b+fi4lq3bl1tba2SkpK4uLi1tTUksbGx+bVPJTU1dfv27Tt37pSTk9PR0ens7Pzw4cOZM2esra1FRERsbGwGBga2bt06bdq0O3fupKWl7d+/X11d/du3b1QqNT4+3sbG5vLly/v27Vu5cmVubm5ERMSiRYs0NDQcHBz27t1raGhYU1Mz4o4uLi7Tp0/fuXOnsbHx7t27U1NTaTRacnLyhQsXjIyMtmzZEhsb29raev36dWdn58zMzHPnzunr6z9//rytrW3NmjUcHBzOzs7h4eEnT550cnLq7e2tr693d3fPzMxsbm4+cOCAra1tQECApaWlq6trc3Mz/ovA9fb2uri4QCvIysry8vKysLAoLCzEcTwmJubNmzdkMtnGxmby5Mk6Ojpv3rzx9PSMiIjo7e2tq6uLiYmpq6v79OmTt7d3WlpacHDww4cPYSiTk5Pz+PFjZ2dnV1fX4uLirq4uf3//xMTE7u5uPz8/d3f3d+/eEb9ZCyWhUv8Pe18dFuW2vs32nO1Wt2KLiDRISyNKNwiSAsKAUlLSSoiEdIfSCFtBCZEuAemQLuluGGKAYagZZub9/ljXmYtL1KN7n71P/L7nDy+E911rvfXUup/7QUdGRnJwcKSmpkIQ1NnZmZKSMjo6CkHQ0NAQUPrJycksLCy3b9/u7e11cXG5ePGii4vL7u4uHo/Pz88PCQmpqqpaXFzs6uqqrq4eHx8fHR2tr68Hln5iYiI3NzcnJyc/P39sbAyFQtXU1HR3d0MQVFdXV1FRQWgD0d/fn52d3dnZSdDICwsLVVVVg4ODhOclJSVlaGj4Q0wX/5V6E4PBREZGnjlzJi8vj/Dl+/v7nzx58unTp0+ePGFnZ0ej0Wg02sTERFVVdWZmJiYmho+Pr7a2trW1lYOD4/HjxxAEdXZ2cnFxJSYmLi4u8vLyUlJSfvz40dLS8ujRoxkZGWlpaezs7M3NzZ/NPjw8LCgoSEtLCwxpa2srMzMzDAYbHx+/c+eOjIzMwMCAkpKSrKzs/Pw8AoG4deuWiIgIAoFIS0ujoaEpLy+HICg+Pp6BgeHDhw9v3rw5fvy4u7v7Zxf45MkTMjIyED4EBgYKCgqWlpaura0ZGBj8/e9/f/DgQW9vr5SUVFBQ0OvXr1lZWcPCwiAIevz4MTMzc1dXV2JiIhsbG8ivubi48PLydnd3R0VFnTx5kpiY2MLC4uBdraysZGJicnJygiBobGxMSkpKUlLy5cuXVFRUnp6ejx49EhAQyM3Nff/+PRsbGxUVVVBQUFFRkaKiIjs7Owjqg4KC6uvr4+LieHh4Xr58CVbOzc3d39/v5eVFTEyso6Pj6uoKPGtLS0smJibgJ8JgMFFR0ZmZmYcPH5KRkRUWFkIQ5OTkxMfHFxsba2pqqquri8PhamtriYmJAQmWpKTk4cOHb9265ezszMLC4u3t/dnlEF4Mb29vUlLShISE169fh4eHNzU16ejo+Pv7Z2RkEBMTP336FGgrTU3N3d3dgYEBdnZ2UVHRra2turo6Xl5eLy+vxcVFExMTUlLS5ubmsLAwIiIiRUXFqqqqkJAQYmLitLQ0/L7YFo1G3717l4KCArAxUFFROTg49Pb23rx508nJyd3d/ciRIwEBAb29vXx8fJcvX3ZycgKdEby8vBYWFsjJySUkJMrKyhwcHIiIiG7durW5uZmQkEBPT5+fn9/Y2MjKypqYmKivr29gYJCRkQE22cDUIyMjsrKyZ8+eDQ8Pz83NZWZmJiIiKikpmZmZYWZmtrW1nZmZERQUJCcnj42N9ff3P3r0qKCgIHAabty40dPTExQUBKIuampqdnZ2FAqVlpZmYWFha2sL2MtCQ0OnpqZYWFgoKCjCwsL4+PiIiIhu3769tLS0/7a3tbUJCwvDYDAIgpaXl9XV1U+cOBEdHY3BYKytrT09PVtaWqSlpU+fPh0dHV1QUEBOTk5BQREfHz87OxsZGWlpacnPzy8nJ1dZWRkTE8PJyXn37l1JSUk+Pr719fWenp5Hjx7Z2tqqq6szMjKmpKQMDw/funULBoNlZmYqKipycnLm5+cD797Ozk5GRgYGg4FIqKOjw8nJydbW9u7du83NzSAUuHXrlri4OCHC+B75r9SbCARCR0eHjo5uZWUFj8fD4fCCggI5ObmHDx9mZGRwcXEJCwsvLy9nZ2eTkJA8ePBgZWXFwsJCWFi4qanJ19f38uXLiYmJ8/Pz9vb2JCQkYHeSjIzsyZMnFRUVHBwcysrK3d3dhoaGV65cARRNQPB4fF9f39jYWGJi4qlTp2RlZdfW1pKTk0+fPu3n5+fq6nrixAljY2PgkYEAJCsri56eHiQKYDCYoKDgzMwMGo1WVlbW09MrKyuTlZU9deoUMMsEwWAwenp6d+7c6evr29jYkJeXv379OgKB6OrqYmBgEBISWlxczMvL4+TkzMzMlJeXl5KSmp+fb29vZ2FhuXfv3tDQkJycHIjW19bWbt68aWVltby8bGxsTEpKSkNDA17oz8TPz09ISKi0tBSCoKSkJGZmZjc3N319fVpaWjc3N1NTU/Anf3//8+fPg+24kpISenp6oLKBrK6uCgsL37t3D4lEzs/PS0pK3r9/H4lEamlp/fLLL0BlQBD06dMnFhYW4CRWVVWxs7M7OTlNTU2JiopqaWltbGzs7OywsbFJSEjAYDA5OTlgALy9veno6ACxy/nz52loaHp7e729vSUlJQlp7v0PC/zQ3d3NwcHByckJekebmZlRUlJGREQoKSlZWlpOTk7W1tZeunTJ19cXgqD3799zc3ODlLeJicmtW7eARjA1NVVVVe3u7tbU1GRhYQFvxdu3b8+dO1dWVrZfb46OjnJxcYGkSktLi7y8vKWlZUhICCcnZ0ZGhoWFhaysbHd3d0tLCwsLy/nz56Ojo+Pj4ykpKbu6utra2i5dupSYmAhBUFdXFxsbm5ubGxKJvHPnjpSUFAqFio+PP3bsmK6urpWV1WeJHQiCRkZGlJSU5OTk8Hj8xsaGgYGBgIDA4OBgWFgYHR1ddnZ2f3//jRs3wIvR2Nh45coVW1tbkPKCwWA4HM7T05OIiIiHh8fDw+PVq1e1tbVsbGzh4eEQBD179gz0ph0bG+Pj4zt27NijR48eP3585MgRdXV1QtgHbkJQUBArK2tOTg4EQYuLi0pKSj///HNSUlJfXx83N/fTp09HRkYkJCTU1NQgCOrr6xMREQHOZmxsrJqaWlFRkaOjo4iISFtbW3JyMmDsFRYW1tbWbmtrU1VVNTY2Hh4e9vLyoqCgyMrKam1tZWRkJCMjMzMzu3///vnz51+8eBEVFSUsLOzp6RkZGamrq5uZmTkwMGBkZPTgwQM/P7+ff/45IiICjUbv7e3JyMjIy8v/0NbQf5/e3N3draioYGdnFxERAR2H/P39ubm5DQwMlpeXwUdCRUUVHBysoqJy7NgxcXHx6elpeXn506dPp6enP3z48PDhw5aWls+ePTt//vyJEycCAwNjYmKuXr3a3Nz88uVLamrqN2/ezMzMCAgInDx58jOoo6qq6u3bt+Pi4ri5uYFr6ebmdvz4cX19fXp6eiIiIiMjI3t7+6NHj9rY2DQ2NiooKIAEa05OzpEjRxgZGfPz84eGhujp6ZWUlPT09A4dOnT27NmEhATCFHg8fmJigoWFRU5Orrm5uauri5eXl4GB4dOnT+np6efOnYuPjwfbYkJCQgEBAQBFUFlZaW5uDqhOCwoKSElJlZWVm5qaQHz9+PFj0KXZ2dk5LCyMmpq6vr5+ampqf5yuqKgoKyvb09MzPj4Og8Hk5eWrqqqkpKRERUU7Ozvn5+cHBwcXFhYkJSWvXLnS0tICQVBSUtKpU6dSUlJWV1d7enpKS0vT09MvXbrk6em5tLRka2tLRETk7Ozc2NgoJiYmJycnJCQkKytbXV1tbm4OPsLp6ek7d+78/PPP8fHxFRUVZGRkwIsHitvFxUVYWFhBQWF1dbWqqoqVlZWHh2dhYSEqKoqcnDw6OnpnZ0dGRkZISKi7u3t7e3v/NhdItMHh8OXl5RcvXpw6dcrIyKixsVFERISUlNTT0zMxMXFhYWFvb8/T0/P06dNxcXG7u7vBwcEcHBwlJSUlJSW0tLTp6ekQBLW0tHBycoaGhtbX1/Px8T18+BCCIGCHhISE9m+gQRCUkpLCzs4eFxcHQVBJSYmSktLjx4+vX7/OxsZ27969oKAgEE7GxMSQkZH5+fktLCwYGhrKysouLy8/efKEnp4ecIxFRkYKCwsXFBTk5uYyMTH5+Pisra3Z2NicOXMGJG0IcSXhIdbV1QkLC3t4eEAQtLGxwc/P7+Hh0dLSAnYCVlZWCgsLWVhYYmJi8Hh8eXk5AwNDXl7e27dvKSgonj17hkKhtLW1r1y58v79ewiCFhcXNTU1NTQ0QMxraGiooKAwPT2dkZFx6NChu3fvTk9PW1hYkJCQJCQkEOJ08IXCYDAODo7h4WEIgjY3N319fdnZ2UdHR/38/Hh5eRsbG5ubm0EiC4KgjIwMMjKy2tra8fFxPj6+yMjI1NRUFRWV58+fI5FIBweHI0eOAKuGw+Hc3NyuXbvW19cHQZCVlZWMjMzg4GBJScnhw4e5ubnr6upev34tIyNTUlIiLCwMut6ur69/+vSpr6/PxMSElpa2oKDAyspKREQEZDB6e3sZGBju37//Q7iu/z69CYfDnz17Zm5u/uDBA0tLSwsLC2dn59zcXEJGIzk5+caNG66urikpKTY2NrGxsevr68+ePTMxMRkYGOjs7JSWlhYSEoqKinJ3d79169bbt2+TkpLi4+NXVlaqq6uDgoKGh4f7+/vV1dVhMBhoUEwQY2NjFhaWW7duycrKJiUl4XC4mJgYWlpaBQUFoL7v3r1bVVUFg8Ho6OjExcUVFBRYWVnt7OwyMzOpqalZWVnfvXvX2dkJtpX09PREREQuXbrk5eVFmAKLxRYVFTEwMFBTU5eWlo6OjiopKTEyMr558yYqKkpMTGx4eHhjY+PBgwfU1NRPnz7V1tbm5+dXUlKSlpamoqISEhJyc3OTlpbm5eWFwWBsbGwXLlxgYWHR1NSUl5cvLCzMzc09f/68oqIiIYEF7iofHx87O3tkZOT9+/dFRUWLi4uXlpbMzMw4OTlDQkL8/PxsbGxSUlLExcUtLCwACObDhw+0tLTy8vJBQUFaWlrPnj0rKiri5OQECoKNje3IkSOGhoaenp5XrlxJTU19+vQpMzPzzZs3OTg4aGhonJ2dbWxsiImJT506ZW5u7uzsDFIltbW1kpKS/v7+jY2NN27cUFFRqaioUFdX/+mnn0RERIqLizU1NWEw2OzsbF9fHz09PSUlZWBgYGZmZldX1/6Htbe35+XlZWpqWlJSIicnd+vWrdbWVl1dXRYWls7OzoKCgoCAgPn5eU1NTVJSUjMzs97eXn19fbBb/fr161OnTiUmJvb09GhqahIREeXn51dUVFy/fj00NHRhYcHV1ZWPj+8golZLS+vq1avl5eUzMzMuLi7m5ubFxcXHjx+Xl5fv7Ozs6Oiorq5eXV3V19cXFhYGOTsuLi4TE5OmpiZ1dXVxcfHS0tLNzU11dXVRUdHk5GR5efljx44lJyd3dnZev37d0tLS2tpaWVm5tLR0dXWVUJ6/t7cXHBx89uzZtLQ0FAqVm5tLTk6enp5ubm7+t7/9zcTEBIFABAUFUVJStrW1LS0tGRoaioiIZGVlSUlJXbhwobS0tK2tTVpampAy6urqAiH/2tpaTU0NDQ3N/fv3t7a2nJycKCgoWltbR0dHBQUFhYWFh4eH91us0dFRMTExbW1t8N/h4WEREREbG5vi4mJGRkYREZG5uTlPT09aWtq8vDwEAmFiYsLGxjY3N5eenn727FkVFZX4+PiqqqrNzc2+vj4BAQEJCQlgJCYmJiQkJDw9PXd2dgYHB5mZma2trbFYbFBQ0OHDh+Pi4qampjQ0NOzs7KKjo8nIyIqKiiAIwmAwaDS6tbVVSEiIjIxMV1fX3d2d0M8xIiKCmJgYRIffL/99ehOHw23/QzY2NjY2Nra2tvZveWMwGCQSubm5icFgdnZ20Gg0DocDmBiAZEahUGtra2CrEYVCodHo3d1dwq4lGo3GYrEYDAaFQoGRCfYcnItAIFZXVzc2NsApOzs7a2tr6+vraDQaiURubGxgsdjNzc3l5eWVlRUkEgkWAw4DxKNoNLqlpWVkZGRzc7O/v7+urg4Oh0P7HAcUCpWfn9/Q0LC9vY1CoUpLSxsaGnZ2dra2tjY2NvB4/O7ubmNjY3l5+fLyMhwOLywsrKioGBsba2lp6ejo2NjY6O7ufvv2bU1Nzfz8/Pv37+vq6lpaWtra2jY3N5eWlnJycoqLi7e2tggzvnnzhoeHR1JS0sDAIDAwcHh4GDSmb29vf/TokampKejDvLS0VFBQQMhdIJHI1NRUbW3tBw8egK8dg8HEx8fr6uqGhoY+f/7cwcGhsLCwrKzs4cOHU1NTw8PDVlZWbm5ura2twcHBt2/fDgwM9PHxcXR0fPHihYKCAiMjIy8vLz09vb+///r6OhaL9fX1paSklJGRcXR0VFBQMDc3b21ttbW1TUpK2t7enp6eFhcX19PTi4uLU1VVDQ0N3f+q7O3tubm58fDwSEtLq6io5Obm7u3tPXv2jIaGhoGBQVxcHHjud+7cISEhefLkSUtLCwwGu3z5clZWVktLCyMjIwcHh6qqqpSU1OXLlyMiIiwtLS9fvmxsbGxpaSkgIJCQkHBwi9bc3FxaWjoiIsLAwAAGg01PT09PT6urq1+9elVXV1dTUzM+Pr6+vl5ERARsamdkZJw6dUpERKSiogIGg5GSklpbWzc3N0tISICdz+vXr584ccLX17ewsJCBgSEtLS0nJ4efn5+Pjy8lJYUAX0MgEHZ2dseOHXNwcKirqzM3N6eiohIREdHS0mJjY+Pn509ISLCxsfn555/d3d1HRkZA7uLWrVtMTEwMDAxJSUleXl4iIiIALwxB0KdPny5evGhgYBAaGiorK/vTTz9pamqWlpbevHkT9LOpra395Zdf5OXlExIS9m+qDA0N6erqurm5gf92dnaeOXNGXV1dRESEiIhIWFi4ra3t3r17P//887NnzwoKCoAznpWV9fr16wsXLgQHB4+MjMTExLS2tubn5/Py8oaEhIChCgoKzp075+7u3tHRAdqMm5mZdXd3KygoSElJ7e3ttbS0nDhxQkdHx87O7sSJE2CD9N27d21tbQ0NDTdu3DA1NZ2YmBgcHCwoKADvv7KysoCAAEAEfr/89+nNb8sXoQY/Cqf47PjPcEh/ZORvnAj0FOG/BAMOtPnBg7FYLGGQvb29gyh3YACgf9S9ENAqeDweQC8Jl7a7uysvLy8kJFRTUwOHw/dD/3A43Pr6+uLiIqH6CIPBgLPAgBgMZmlpaWlpibDInZ2dxcXF9fX17e1tJBIJNujW19fBMtbW1sD4m5ub8/Pz6+vrm5ubKBSqurpaUFAwICBgYGBgZGSE8B2iUKiJiYmpqanV1dXl5WUEAoFGoxEIBDBpe3t7cDh8dXU1LS1NVlYWbEYR7hsOh0MgEFNTU5OTk3A4HOyobmxsTE1NDQ0NTUxMbGxs4HC4xcXFycnJ1dXVnZ0dOBw+NTUFDMCnT5+Sk5NHRkYWFhZmZ2enpqYEBAQUFBTevn2bl5fX398P7sl+s4rH4xEIREVFRWJiYnZ2NthBxuFw09PTiYmJ8fHxNTU1YPF1dXUAaDw1NfX27duqqqq1tbWysrL4+PjR0dHt7e3w8HB/f//R0dGPHz/GxsZ2dXVNT0+npqZubm5ubGw8ffo0JiZmfn6e8Nrs7e1lZGTcvXu3pqZmY2OjpKREX18/Ojq6oaHB3t7e1dV1eHj49evXd+7cKSsrg8PhFhYW2traJSUl8fHx5ubmFRUVz58/9/LyWl9fB5cDh8MtLS3v3LljZ2eXmpoqLS3t4uJSXFxsZWWVlJQEQVBTUxMVFZWenl57e/v+V3dhYeHJkyeEgpShoSHrWHd6AAAgAElEQVQaGhpOTs7s7Gw+Pj4aGpoXL15oaGgcOXIkODi4paVFVVWVj48vPz9/fn5eTEyMgoKCkZHx3r17c3NzkZGRt27dArcRgqDx8XF2dvYLFy5wcXEZGhrS0dEZGRnFxcVJS0sD3Zqenn7ixAlJScno6GhGRkZubm5RUVElJaWPHz9OT0+DhhFmZmYwGMzDwwOJRNbX1/Pw8AQHB/8oY8P/mt78//KjgsPhKisrL1++LCQkBBJSf73s7u4+ffr08uXL2dnZv2+Ejx8/5uTkEL75f5XshxPGx8cfPnw4ICBge3v7izWsBMHhcKurq59BEXd2dj6rmSEoXILSwWAwhJGRSCShImh3dxdYHQLednV19WA+bnNzEw6HAxWAwWAWFhaAdVlaWgJZLBQKtbCwAAzq4uLi7OwsiN4WFxe3t7dBIEUYDYvFLi8vT05Ozs7OotHomZmZpaWljY0NOBwOFra9vT04ODgzM/OZ0sFisR4eHubm5uAaAUqhv78fi8WOj4/39PTA4fCJiYnu7u6lpaXd3V0QiBAi8ZaWlo8fP46NjRFM2v4bNTAwkJycXFVVNTMzMzw8PD09DYfDx8bGAK5gZWWlp6dneHh4dXW1sbExIiIiLCysoaFha2sLi8X29PRERkZGR0dXVlbOzc3NzMwoKys7OjouLi5CP+gD/X+9+X9agIu0sLBQX19fXl5OQJP8xTI0NPT06VMbG5uAgIDfxx4AMiHQn1lcBLCo0dHRf9L4/0sSHBysrq7+o8WL3ynf/4gBU9r+3+zs7IBwB2BszMzMgK+wv3bge+TfoDdxONzExERXV9dBS/X9sre319/fv7S09H+Qs3Z/YPjHh9o/yGf70fuj+z9PQPA+Pj4+Pz/f29sLssafHfCdQ/0+Jo6vVeB9dkx5eXlmZuZBMq2Dqz04zn6g0v+2gGvs7e3Nz8+fnZ2F/tVX/T0v/2dP8OCRSCQyPDzc19eXsOv7X6A3sVhsenq6lJRUZmbm79N6GAymqKgIbIXvB0D8X5CD78Sf9DXi/1Ewh8fjl5eXAUjrL+7kAzbWoD9Z44Ar3S8/NN3BR/BF5fsXWKD/KMFisd/OZvwF8jUruLW11dDQ8Eeiq39PnB4YGHj+/PmsrKzfdzoGg/H19QUFhf9p5Dp/tuDx+O3tbYBaBVQdf95EhJ/n5uZUVVVpaWkPwsv/JJmbm/P19TUzMwNA0T9VCHpz/29+aAQ0Gt3Y2Jidnd3d3b1fWezu7nZ3dxcXF8/MzPwfDIz+h+V36k3wYmGxWIDI2dvbm5ycJNQMAFlcXEShUDgcbr9LuLq6Ojg4aGZmRuiWjsfjCTC0/Tu5n023/1VeXl4ODAykpKQkAGL+7ZbtR+U7Q9Ev/h6Hw6WkpKipqR2sjD541h9xc9bW1gA2eGdn59KlSwICAoRatO8Z80e9tv0/wOHwK1eu0NPTf4/e/IOuHOHc7OzsxMTElZWVHx0BjUbHxMSwsrIC8Pzg4GBqauqnT592dnaePn0KuGZ+aIUIBAJAd6Ev3cZ/GocePP77D/6hw/6NcjANsv9P4AeAbcjOzv5iDSUOh6uvr8/Ozv4dedg/pDdXV1cTExMfPnwYFBT08OFDJyenhoYGkCMrLCx0dXUNCgoCuDMIggC1wYsXL5ydnVlZWR8+fIhCoSYnJ2NjY93d3UNCQsLDw0El38G5CLa6ubk5KCjIw8NDUVFRWlp6dXV1c3OzvLw8MjIyLi4uJydnYmJienq6sLCwoKAgKSmpubkZ3N+SkpLs7OycnJyUlJSOjg5Q3DI/P19TU9PY2Li1tVVaWlpbWzs/P//hw4f09PTi4uKUlJSysjLQiuPjx4+EELW6ujozM7O+vr6trQ2wKnxRFhYWAEhzbGysubl5ZWUFi8X29fX19vYSdjA6OzvLysqmp6chCEIgEK2trfPz8xgMZmhoaHp6moCbqaurKykp6e/v39jYWF9fHxsbKy8vr6ioAIjOpqamgYGBlZWVqamp/v5+UAWEx+P3GyE4HN7T0zMzM7O5uYlEIhcWFsBu7Pr6OsGqLS8vz87OLi8vA/DQ6Oioq6urubk5CoUaGBggIyPz9/dfXl6em5sjjIxAIMA+JhgNiUSC0QAeFvrBz2+/R7azs8PJyWliYvKjLJPfnvFrgRsQb2/v+/fv/47wDWCAyMnJAb1bTU2NkZERQAiampqys7MTaiK/qAQPDjgxMeHg4AA+h2+c0tvbOz8//51qdGJiAoC9Pzv4a7xBeDx+ZmZmfn7+P7OrCsF1AzDM4eHhhISEzs7O/WmWpaUlVVVVLi6u2tragyPgcDhbW1seHp7KykroB9/VPxSnj4+Py8vLg6IrKysrOjo6SUnJ2dnZ1NRUDQ0NW1tbFRWVI0eOeHp6bm1tJScna2lpAbQzMTFxXl4eHA63tbVVUlIyNTWloKA4e/bs27dvD85CeNdramp0dXXl5eX5+fmPHj0aEBCwsLDw/PlzLS0te3t7RkbGU6dOpaWlhYSEUFFR3b17FxBSLC8vv3z5UkpKysTEBDAdODs7Ozg4nD171sjISERExNTUdHx8/MqVK5ycnEFBQWJiYmfPnlVWVmZiYqKiourp6VlYWLCwsAgODl5ZWSkrK1NSUlJWVpaRkbl16xYg6fiiVFZWKioq3rp1C1Dg2NnZRUREqKioqKmpzc7O7u3tpaWlubq6ysrKGhsbLy0t1dfXX7t27dGjRwkJCbq6uh4eHqurq0NDQ/7+/g8fPrx3756ysrKXl9e7d+8CAgKkpaWrq6vX1tYiIiL09PQAcY6/v//t27dBmd3AwIC3tzeo2AMg8ydPntjY2KSnp1dVVTk5OYWEhOTl5Tk7O9fX16+urhYVFUVFRQUFBdnZ2b17925iYsLW1vbIkSMGBgZDQ0PJycnMzMyJiYkRERGurq6jo6NoNLq8vNzX1zcoKOjly5fglJCQkNLS0vr6el9f39TU1NXV1W+8i9vb2x8/fnz//n1FRUVFRQXwCPb29qqqqmpqavz9/UlISGJiYiAImpmZqaioaGpqqq6uBvj/7u7uiooKoNCrqqoaGhqqqqoaGxuXlpbwePzU1FRzc/N+4pwPHz4ATh38P5oFHFzPzMxMbW3t3Nzc2toasIjb29t9fX1ra2t4PH5kZGRkZGR3d3d9fR1sYY2Pj7e1tYEiy83NzSdPnigoKPT19S0tLZWVlVVWViKRyO7ubhUVFWNj46mpqe7u7sXFRTD1zMzM0NDQ8vIyCMgAwHNqampjYwONRm9sbExPT9fV1QGD+kXZ2tr6+PGjurp6Wloa+M3Ozg6wzRAEYbFYApclkNnZWTs7OwIWHYKg/az7X9SefX191tbWPwoI/ysFDocXFRWButWKigoeHp4XL17sv2osFissLKympvbFGGJ7e1tPT09cXLy9vf1Hp/5D/mZ7e/u1a9fk5eXBNdy8eZOHh6egoODatWvPnz+HICgqKuratWuZmZlZWVm8vLzp6embm5sWFhbc3NyfPn1ydHSUkZFpb29fWVmRlpa+cePGF903MFdTU5O0tLSFhcXq6qq7uzuosI6Ojubj4ysqKsLj8YDpq6Ojw8PDg46ODpRV9Pb2ZmRk0NHRgXrhu3fvXrlyJTMz09ramoiIiJGR0cnJKTs7u729nZaWloSExNnZ+cGDB2JiYjk5OREREcePH09NTV1bW3NxcfHx8Xn16hU7O/uzZ8+Gh4eFhYUFBQW/FilDEFRRUcHKynr69GkZGRk6Orpjx47x8/NTUlKys7OPjY3l5OTIy8u/evVKQ0ODnJy8vb29uLiYiIjo8uXLCgoKNDQ0N2/e/PTpk7q6OuATKigoOHr0KCsra1RUlImJCQ0NzadPnzo6OsjIyOzt7a2trWEwmJeXFz09vbS0NARBb9++JSEhycjIqKmpkZSUfPz4cVxcHAUFxf3797Oyss6fP3/48GEuLi52dvacnJzo6GghISEvLy9Qg2Fra9vX1ycsLExBQVFYWDgxMeHs7Kynp+fv76+mpgZodd69e3fz5k0TExMNDY2jR48+fPiwuLiYnJxcUVFRU1OTmJiYkZFxP/HiZ4JEImNjY6WkpKSlpWloaEhISFJSUtbX15OSkoSEhAwNDc+dO0dLS9va2goY8jU0NO7fv3/x4kV+fv65uTkdHR1QbWJnZ3fu3Dl5efmbN28yMTEBPPbLly/5+PgQCER3d/eTJ0+uX7/OwcFx7ty5wMBA6OtuhYuLi5KS0sDAQE1NzbVr1wwNDZOTk+/evRsSEpKbm6unp3f//v3Jycm6ujodHR1bW1t/f39lZeVHjx6tra0hEAgODg5ASZeYmMjLy/v69WsIgt68ecPExOTv729tbX3v3r3q6moIgtra2tzc3GxsbJydnbOystbX15ubm11dXZ8+fern59fZ2dnQ0BAWFlZeXk7g+j242rq6OklJSQYGhtTUVBwONzY29u7du9jY2Ly8vNXV1YaGhtDQ0LKysvLy8rKysuHhYX9/fwoKClBDubKyUl9fHxUVVVBQsLy8vLCwkJGR0dfXt7i42NzcPDg4uLm5OTk5aWxsfOHChZaWlvHx8c7OTkB0C4fDh4aGvoYVA+WPnZ2dgBRxZWWlr68PrH9+fr6+vr6xsREAaeBw+KdPn0CAPDIyMjg4CEKW5eVlUGgLYJgES3NQEAiEvb09Dw9Pbm7u9vZ2S0sLIEgFf52bm+vv709NTWVgYAC8JHt7eyMjIxMTEygUCuBwBgcHKSkpDQwM5ubmFhYWFhcXvz8H/Yf8zZSUFD4+PuAUdHd3CwgIWFtbm5iYWFtbz87OYjAYOTk5VVXVDx8+qKqqgnrViYkJSUlJ8Jmxs7MDKh3AiPPgwYOvTbS7u6utrc3ExNTV1bW8vHzv3j0FBYX+/n5BQUEHB4etra3+/n52dnbAUFlXV8fMzCwkJDQ+Pj43NycnJ2dgYLC0tIRGoyUlJfX19QcHB+/cuUNPT19TU4PFYgFt7blz5yQkJMbGxmxtbaWkpIDX/Msvv3h6ejY1NcnLy5eUlIiIiJibmwPyWk5OTjMzs4NLJTzmyMhIMjIyb2/vrKwsEhISDQ2N6upqUVFRBweHjx8/srOzu7m5PXv2jJ2d3dPTE4fDxcXF/fTTTyoqKrW1tTw8PObm5rm5uVeuXHn06NH29raPjw8xMXFcXBxgeFNWVkYikRMTE6ysrNra2h8+fBgfHx8YGFBUVBQQEEAgEJmZmVJSUq2traKiopaWlisrK3V1dTw8PGFhYRUVFcePH6ejo4uNja2srBwdHRUVFfXx8UGj0XFxcaSkpLGxsf39/by8vBoaGhAETU5OkpGRSUpKysjI5OXl4XC48vLyGzduPH78GIPBvH379vLly/X19e/fvz99+vSFCxeKi4vl5eUZGRm/xiWMxWJDQ0NZWFiio6MnJibk5OR4eHgGBwefP39OT0//7t27lZWVq1ev6ujoDA8PGxsbKysrz8/PA9YPExMTOByuoaFBREQkKCjo7e1NQ0MDKCBZWVkfPXoEQVB2djawx7dv3wZsp05OTiQkJKCa6ItxOgaDkZGRYWRk7Ovr+/jxIxUV1enTp+/cuSMmJkZFRSUrK3vjxg1paemhoaGUlBRiYmJubu43b948efLkzJkzL168GB4epqOjA+N7eHgQExMD4uGwsDA2NrakpCRlZeWYmJjJycnu7u5bt27Z2dn5+/uTkpIaGxuPj48bGxvfvHnT1dWVm5u7pKSkvLyckpLy6dOnX9ObOBwuNTX1zJkz2trag4ODDQ0NFhYW9vb2urq6DAwM1dXVTk5OJ0+eFBAQ4ObmVlBQeP36tby8/Llz57KyshAIhI+PDwwGU1NTO336dFpa2osXLy5evGhhYREUFHThwgVQB5mUlHTo0CEWFpbQ0FATExNiYmJbW9u9vb3Hjx/LyMh8ka0ZgqCZmRlg86KioiAIAgyHs7OzMzMztra2zMzM7OzsFBQUnp6emZmZbGxsurq6/f39qqqqPDw8NTU1i4uLLi4ubGxs1NTUjIyMYmJiiYmJnwFmCHfjt99+IyEhISEhKS4ubmxsFBcXByQPeDy+oaHBw8PDzMyMiYkJ7KNgMJj8/Py7d+86ODj4+vq6ubmtr6/n5eVRUFCkpaVVV1fb2dllZGR8PzjnD+lNOzs7Dg6OoaGhtbW1x48fc3BwlJWVXblyxdnZeXV1NSIi4tChQ05OTlVVVQICAi4uLgsLC7a2toDlydvbm4uLq6ioCIVCWVtbnz17FrgDX5SmpiY6OjoYDLa1tQWYNx8+fBgeHn7x4sWcnJzt7W0/Pz8aGpqoqKjp6em+vr6EhITTp097enrGx8eTkpLGx8dvbW2FhoaeO3cuIiKipqaGwPQFQRAKhdLT06Ompq6rqxsZGbl69SoMBtvZ2SkpKWFnZ1dVVXVwcIiIiEhISCAlJQU+lLe3NwkJyWfV0Ptlc3MTcEp2dHQEBgaSkJBkZ2cD1rW0tDR/f//Tp0/z8fFZWVllZGRsbW2trKwARqW2trampiYaGhrgOAgKCsrLy6elpd28eVNAQGB0dLSlpYWent7e3h6JRG5vb0dERFy6dMnOzg6EaXfu3Ll+/XpOTs79+/fDwsL8/PwIJJ7h4eHKysrZ2dmPHz8+efJkVFQUqMF3dHQUFBQEBDOOjo5KSkpjY2OAKfm3336DIAjQUpw4cUJQUBAE/hoaGvz8/JOTk0gk8u7du9euXQNv/NmzZ93d3SsqKri4uGxsbL7Y4AiCoE+fPrGysj548ACHw42MjPDz88NgsO7ubiEhIScnp93d3dbWVmpq6tevX2dmZl6/fh1wcf/2228XLlwoKCgA/I+A5zguLu769esFBQUbGxvS0tKA0CwgICAoKMjKykpaWhrUMiopKQkICIBdxC/G6fX19bS0tAYGBng8Picn58yZMwYGBpWVlcDHLykpERcXNzQ0XF9fNzc3//XXX1++fLm3t5eVlXX8+HE3NzfA7goCRk9PTzk5ubq6OiQSee/evaNHj+ro6MTFxW1vb4+Pj0tISDg6Oi4tLQE/w8XFBYlEampqUlFRAUaCra2t5uZmSkrKV69eQV+pG8bhcNnZ2aSkpCkpKcClUFNTa29v19XV5eXlHRkZiY6O/vXXX69evers7FxUVFRVVcXLy2tkZIRGoxMSEmRkZBoaGry9vcnJyQHHNg0NzcWLF4ODg7W0tAQEBEZGRt6/f3/y5MmQkJD+/n53d/fDhw97e3uDdgZqamoHQSyEbGNxcfHly5ctLS3BI2NgYCgqKoLBYPr6+r29vTk5OUxMTG/evJmbmxMRETlz5oyXl5eBgcGlS5eSk5Pt7e3l5eWbm5vr6upoaGhu3LhRVVX1mW9LeHZeXl5nzpwJDQ3FYDAZGRns7OyxsbE4HK6mpkZUVDQqKqqvr4+Dg8PS0hKLxWZmZgLSgLS0tKNHj2poaCwuLvr6+iopKYEGOYaGhsPDw9+/wfj79ebq6qqioiKglvLz87t+/XpaWtr8/Dw9Pb2oqKidnR1IJvLz87u6uiorK/Pz82tpaZ08efLnn3/W1tbW09NjYmJ69OiRubk5MTHxoUOHzMzMvub/19fXs7KyysvLAyeOmJhYS0tLVFT0+PHjISEhgPrh119/lZSUZGZmtrGxaW5u5uXldXZ2joyMvHjxop+fn4+PDxUV1aFDhx48eGBkZCQkJERIFS8sLFy7ds3U1HRjY+O33347fvw4LS1tdXU1oKQ7ceKEnZ3dwsKCm5vbsWPHPnz40NraevXq1UOHDvn7+3+N1r+jo4OFhcXa2np4eFhKSkpYWLivr8/IyOjUqVMxMTFubm6ABm1ycrKhoWFmZqagoODkyZP379/f3Nz09/c/ceIEIGixsbGhpaW9f/9+RkYGyIpGRkYeP37c2to6IyMjMDBwcHBQVVWViYmppqYGh8MFBgZSUVG5uLg4ODiMj48bGhpKSkoODAz09vZycnIqKyvn5eWJi4uLiooC0zo7O3v58mVhYeHx8fHq6moaGhpdXd2ZmRkLCwsyMrK6urqVlRVLS0sGBgZnZ2d6evrCwsKuri4KCgpTU1MsFpubm3vx4kVra+vp6WlAHDs9PR0eHk5HRwdIJA8KHo8PDw+/dOkSSMyFhoaSkpJ6e3tHRkZeunQJ8FppaWmdO3euoaFBT09PQkJidnYWEEfy8/Nvbm4CPidfX9+dnR07OzsNDY3+/n4EAgGi9czMTG1t7Y6OjuvXrwcFBaHR6I6ODjo6Ond3d1DR/8UPw8/P78KFC4BgzdHRkZGR8f3796GhoWfOnImOjq6vr79y5UpcXNzy8rKoqOjNmzfBzpinpycbG1tZWZmioqKJiQmoGpSQkDAyMtrb22toaODg4Dh06BA5OfmbN2/29vZevHhx5coVEK2HhYWJiYnl5+fj8fjCwsLTp0/Ly8uDWNXZ2VlSUhIQZn9Rb+7s7BgYGAgJCQ0MDGRnZ3NxccnJyenr6xsbG7e3t8PhcB0dHVpa2uzsbIB1SUhIAOlpwDCioKAQGBgoKyubnp6+u7ubl5dHRkZmZGQ0PDyso6OjqKi4tLTk6urKwMAAcqDe3t7U1NSVlZXx8fHk5ORfpA4i3FUQ+dnY2EAQFBwcrKOjEx8fT0tLC4y3nZ3d9evXOzs7KyoqLl68yMPDU1FR4ePjw8PD09HRISoq6uHhsbOzU1lZSUZG5ubmBkh5vjiRtrb2tWvXwF0KCAi4evXq0NBQbW2tgIDA48ePEQjE2NgYAwNDYmJie3u7lJSUs7Pz9vZ2SUkJoJpeWVmRkpJSU1NTU1OLiYlZXl7+9p7hZ/L79WZ5ebmUlNStW7e8vLwAkxsajcZgMFFRUaqqqmFhYXFxcQYGBlFRUZOTkykpKdra2qGhofn5+Zqamjk5Oe3t7Y6Ojnp6el5eXnfv3r19+3ZRUdHXPJSVlZVnz57Jy8t7eXklJibq6OiEhYXV1dVpamqqqak5ODgYGBioqakFBgba29vLyckZGhqamJiAzWVNTc3bt287ODgYGRlJSkoC7jIXFxeCyltaWtLV1X3//j0ej3/x4gUbG5uRkdHi4mJrays3N7ecnBzIuhYWFjIxMbGwsLi4uIiIiJCRkT179uxrnH3JyclCQkI5OTnA+kVGRsLhcHV19V9//dXLywsMJSgoqKqqqq6u3t7enpCQcPbs2bKyMkCOfejQofv376NQKC0trV9//RWQNUAQtLW15ezsfPjwYW1tbQ8PD1paWk9PTykpKdBlCIKgmJgY4OPD4fCdnR0bGxtWVlZ9fX0dHZ1jx46xs7Obm5uLi4sTuMKAzaCgoFBRURESEjp06NDp06e9vb0tLS3//ve/w2CwhoYGNjY2JSWlxsZGNjY2GRkZwGqjr68fExNDQ0MDyM9zc3OpqakDAwNxOBxoyyErK/tFCBFo0gmMWXh4ODU1NRERkYGBgZOTEzk5eXJysp2d3a+//nrq1CkDAwNKSsobN268ffvWzMzsp59+YmZmTk1NffDgAQMDAyiPExMT4+fnB2gHLS2t48ePa2tr9/f3j4yMkJOTR0RE9PX16ejoHDp0yN7e/htRmIuLCyMj48OHD3Nzc8XFxVVUVAC/HB8f3+TkZHBw8PHjx6Ojo7Ozs5mYmDw9PSEIKisro6Ojs7e37+3tpaamDg4Onp+fLykpuXz5spmZGRqNDgoKEhISevLkiZCQkLOzc2dnJxsb27Vr1wDkg4+Pz8jIqL+/v7KyEmypnT9/vqysbGNjg4uLy9zcHGzrf/FLBtuYFhYWe3t7ZmZmhw8fdnZ27u7uBvtI/f39ly9ftrCwAMp9aWnp5s2bnJycg4ODmZmZx44dA3alv78fuI2AjLK1tbWiokJYWDgiImJ0dFRSUlJRURGCIAwGIy8vr6urC5qssLOzA+L0r0lfXx8nJ6ezs3NDQ4OVlRVwNu/cuYNEIsfGxpiYmPT09NBotKOjI9jF7enp0dbWdnNzW1tbc3d3FxMTCwkJUVJS0tTUBMHNFxXZ2NgYOzu7qanpzs4OSP3JycmhUChnZ+erV6+C+2Bvb8/Hx1dVVWVhYSEmJgZ+GRYWRk9PPz4+PjY2RkVFxcjISE5OTqCA+v6Sh9+vN8PCwuTk5FJSUgDTLUHlbWxsAFjMzs7O7Ows4DLY2NgYHR0F5mtiYgLorIWFhf7+ftAobWJiAjSQ+hrqYn19vbu7e3JyErADAKzo2NhYW1vb+Pj4zMzM2NjY6uoqAoHo6OhoamoicKiMjo6CY2ZnZwcHBycnJycmJkAFGBCAuQHrXFhY6OzsBK8saF5G2E/c3Nxsb28vKirq7e3t6elpbm6emZk5qOjBJUxPT3d3dyORyOXl5a6urpWVFQwG09fXV11dPTY2trGx0dzc/OHDh9LS0rq6uvX19dnZ2Y8fPwJcUXFxcXR0dHl5uaen5927d21sbHR1dUH2Fmhzf3//jo6OxsbGp0+fBgYGpqSkEDBSwPACGko8Hj80NBQYGBgeHl5VVRUZGRkbG5ubm5ueng6iV3Dt5eXlwPKBHjKBgYGNjY0JCQmampoZGRnj4+OgqScKhYqJiTExMXn9+rWXl9ft27efPXvm4+OjoqISERFRVVWlr6/f09MDQZCHh4eAgEBERASw4QfvT0tLC2gW5OzsDIPBODk5w8LC6uvrFRUVjYyMvLy8nJyctLW1ExISHBwcQO+XO3fukJKSCgkJgS49Dg4O4Hmxs7NLSkpOTU3B4XBFRUUCMn9hYUFERISCgsLCwkJZWZmIiEhNTe0boDENDY1Dhw75+fm9ePFCQEAgPj5+eHhYQUHBz89veXlZUFCQiIjI3d3dx8eHnp5eQUHBzMyMl5dXX19/bm6uqKjop59+4uTkbGpqiomJISYmvnr1anp6+u3bt8XFxcfGxh49enT+/Hk+Pr7jx49TUlLq6OjcuHGDiIiIkpJSRUVFTk7OycnJ29ubmf4mZCoAACAASURBVJkZsAScPn2alJS0uLj4i0vF4XD5+fnExMQXL17MzMy0tLQ8deqUq6trZmamra1tenp6enr6mTNnAPcwBEHt7e0cHBwA1vL69WtaWlp1dfUPHz68fPkyNja2oaHh6tWrbm5uWCw2MDDw6NGjMBjs4cOHVFRUwsLCPj4+1dXVtLS0cnJyN27cAL5zWFjYZ0jt/YJCoTQ1NcnJyZWVlT98+DAyMiIuLg6DwUZGRu7evfu3v/3N2Ni4paVFTExMWlp6e3u7sLDwzJkzDg4O7e3tUVFR/Pz8np6e1dXVU1NTX6vdwuPxiYmJZ86ckZWVnZubq6qqYmNjMzExqaqqUlJSMjQ0xGKxqampIGnb0NDAy8sL9k4+fPjAwsKioqIyMjISHBxMTU0dEhLCzs4eFRW1uroK9qD+XL05Pj4uKipKRUUFgg4gX9PW3w+M+oOn/0HB/6OIODExUU1Nzd7eHnyE338394/zu9eAx+N3dnaSkpK4uLjy8vJ2d3eHh4elpaWpqanBniZQGVgsdm1tDfQ7nJubq6urCw4OtrS0BE+EsIb19XXAEoTBYLa3t8G/n00KXhoAhQMmDXDMALa61dVVECttbGwA/AAKhWpqapqdnQUdg9fW1oBdBIdNTEx0dnaCRX7NCg4ODpaXlw8NDY2Pjzc3N8PhcCwW293dDVqPra6uDg8Pb25uLi4uNjY2fvz4EUR2AGk7Ojo6NTUFgu6KigqQVaysrFRVVSUkBwDDaVJSUmVlZXt7e25ubn19/TdaeNfW1qakpExNTU1NTdXV1S0tLa2trTU2Ni4sLOzs7BQVFb19+3ZwcBBkhzw8PBwdHcPDw4G5Ghoa8vX1ffPmzeLiYnt7e0BAwMuXL/v6+mpra0HypLm52dra+tWrV0lJSU5OTi4uLvHx8aCpJ+ju+eTJk4iIiJycnM3NzbGxsSdPnjx9+pTgbX12D3E4XEtLi6Ojo7W1dVNTU1dXl6enp5mZmaOjY3R0dFdXV2VlpZubGwGFOjMzo6enJyQklJaWNjs7Gx0draysbGxsnJiY2NjY2NnZqaWlVVZWBkFQenr6jRs33N3dU1NTxcTEDAwMKioqWltbJSUlpaWlo6OjxcTEzp07FxcX98V8GmGdpqamIB+1t7eHQCAsLS1PnDihqampqal56NAhfX393NxcRUVFQOGelJQEaDRnZmasra1PnDgBFBmBkfaLX1NERMTPP/9MR0fX09NTVFREQkJy586d9vZ2KysrEhIScXHxBw8eHDlyhIKC4tWrVxISEqBXDRcXFxEREdh8u3PnjpKSEsgvUVFRmZub/1At3A/rTXAlcDg8LS0tICDg2/1X/xtlZWXF398fBoOBl+nfJQ0NDQYGBqqqqrq6ujY2NlZWViEhIV8Dgb97905OTk5TU7OqquqvXea/Xz5+/AigqftJfP8MWVtbA/UaS0tL4KsmCAEZ/ll1HBA8Hk8guAMUohAEETJ3Kysrk5OT+0tWVldXvw0139nZWV5eJlCUgg6dHR0dYEAUCgX6boGpsVhsV1dXe3s7sIhra2sVFRUlJSWAMg6NRvf09ACk7fLycktLC6i8aGho6O3thSBoe3u7oaEBGOPOzs6MjIwvVtcQtFttba2mpmZgYCC4BFDrERER8fLly87Ozjdv3jQ0NIDoamRkBABjo6Oj379/n5iYaGpq6uTkZG5uDtDWwCIenAiPx4+OjiYlJb179251dXV6ejopKamsrGx3d7evry84ONjX17ehocHX19fT0/PTp09FRUV2dnY+Pj7BwcHW1ta+vr5g67i2thbssz948CAiImJ6evpP9Df3O5U4HG4/evZ/Q9BoNCib+XcvBOru7nZzc3vw4IGjo2NhYSFQCl/04Lq6uiIjIwkG8y/z0P8T5MWLF5qamq9evfqah/uvEicnp7/97W9f2+/6z5TPFME38Ik/RPj9xd93dnbGxMRoaGgEBgZ+p1ogTDoxMcHAwAB2kxYWFu7evcvOzp6fn//Fqb/zEe+PqzY3N0FKDfCW4vH4/StEoVBgzD8xv4nfJ5/9aX19fXh4+NOnTz/U4eifTvSNA0DJ4J9XnP6fpoC+kf/dL/v52L+W+vjR5MM/Xca/SyYnJ0dGRghlnX9wYd+4w8+fP3/06BHwwv6aO/BPH99B+dqR0D+KggjHfPbDNwb8nokgCMrJyTEyMvL19f2MPm7/D18bam5u7sGDByYmJsnJydHR0fb29s+fP/9iUcnXVvLZgvcf/+07/MV79U/lX8aHhMfju7q6dHV1ra2tFxYWent7BwYGvgbT+R75p9h9DAaTlpZmY2MDMkH/G4LH4zEYzODgYE1NTV9f3w+x5M3OzlZWVg4MDOx/9p99Kvvv6ndaVywWu7S0hEAggMXe//lhMBg4HP5tM4nH4/f29pBIJCATOPhYv/NN/bfI939If6V89hC/v8rl9/GTfo/g8fiZmZnR0dHfXcy+traWkpLi4eHh4eFRVFRE6EHyH3j/oX8tj1xlZeWJEyfAXqebm1tYWNg3MvHfI3t7e4ODg4Taqc8EiUSqqqpSU1M3NTX9kVn+02RnZycqKgrU532NIOqLkpWVxcbG9vjxYwiC1tfXu7q6QOnYZ2oUDod3d3fvb6T1bdnY2AgJCXF0dATkFIRXeXBwMDQ0NCYm5hv71ECWlpZA99CBgQHCR07ouPCv/TCAmv59Y25tbbW1tX38+HF/vw08Hr++vt7a2trW1vZDj+MPCgKBALWPB/+Ew+FWVlYGBwe/E3W4t7e3srLyL28isl8OLgB0J/zdp0P/MAn/a3pz/9Pa3d1dXV1NSEi4dOlSS0sLFotNTEysqKhAo9E7OzvABIH+XOB4wu0g9A4Dsj+vj0aji4qKtLW193OZ7O+FsLq6ys7Orq2tTSja//Ns6e8b+YtnHQwNPjsAg8H89ttvpKSkOTk5PzRdbm4uBwcHwGa2tbVZWVnV1dUddEYqKyvt7e0Jva0nJye/nehYWVkBLSIAHhMseHp6Wk1N7ddffw0PD9/flOazKyJoWAEBAWpqalCVBKS0tNTHx+egzfss2vpacPfFMA2CoKmpqcTExJaWFvDWfeOs/f8CGRkZuXHjBg8PD2g12tvbCxyo6upqVlZWFRUVArjtewSUjXd0dBxUH/uXDeqIAOxm/2KysrIkJCRA1dDBkfPy8m7evJmSknLwKg5Kd3e3i4tLdnY2ULjf5lv5ITk4DvjN6OhoQkLCF2l6vn+c/1hnE/ojvB6ELnp9fX1ZWVnx8fEaGhrXrl0bGhrKz88HdDjj4+Px8fG1tbUzMzOJiYmgoKilpSU/P39tbQ2LxWZlZTU0NEAQBDoavn79ur6+vrOzE41GV1VVcXJyXr16FehNJBJZVlaWlpZWWVn54cOHnZ2dqakpCgqK4ODg0dHR0dFR4AugUCjwFk5OTi4tLSGRyKmpqZWVFQQCMTExMTExcfAlBnEoaA4FyuohCFpaWgJdnwj549XV1dHR0YmJCdCaEYKg7e3tsbGx4eHhubm5ubk50MdxcXFxc3NzbW2NoE0WFhZGRkbm5+dXVlb2t94lvBZYLBYOhxPaXaFQKHt7e0FBwdbWVgQCAYfDQfvfhYUFMAKwUigUColEgunAeiIjI0VERN6/f7+9vd3V1VVQUAC8uZWVFQAV2tnZweFw3d3dOTk5a2tr8/PzoaGhRkZG+9GsBwUOh/Py8hIREVVVVYGJtra2Hj9+TEREpKSkRDB7YHDCWft1cW9vr4SExP379/fnbYqLi+3s7ACe/3fL/psJZu/s7JSWlg4PD/9GwPi1r7G/v5+bmxvgvScnJ83MzDw9PUFP5nPnzgUFBf3QZ7y3t+fp6SkqKvrFam6CAzg9Pe3q6uru7v7Zgv38/M6fPx8REXHwXBwOl5CQcPHiRVCB+o0rAgIcGn9//7W1tefPn7958+YP6iMcDodCoQDg+osHODo6/vLLL2Cf539Sfr/eBG9qcXGxtLS0sbGxo6PjmTNnrKysqqurOTg4FBQUFhYWCgoKSElJlZSUPDw8zp49y8DA8OzZMzk5ORISkk+fPq2vr/Pz81tYWKytrYWEhAgJCWlpaV2+fPnatWvz8/MPHz48cuSIsLBwbm4uHA53dXUVERHR1NS8ePEiHx9fa2vry5cvQf2Wtra2oKAgwGZHRUVpaGgoKSldunTJycmptLSUjY1NW1vby8sLFMYctIEIBEJTU1NaWpqKikpJSWlwcHB6etrGxoaNjY2LiwtQbwESJmFhYSoqqsePHy8vL+/u7qakpEhISDAzM/Py8ioqKnZ0dGhpaamoqERFRVlYWACYW1dXl4mJCT8/v5SUlLm5eXt7+/4GvxAE7e7uFhcXGxsb6+npgQq25eVlBQUFU1PT5ORkBwcHLy+vzMxMf3//O3fuGBsbv3v3rqOjw8TExNPT8/nz5+bm5oD4fWtrS0NDQ1RUdGBg4MOHD+Hh4Y2NjRgMprm52c7OztnZOSAgoLa2tqury8PD49WrV0gk0tHR8fTp0yYmJl/LhABpb2+/cOHCTz/9FBAQABRxamrqpUuXiImJwVcNahkzMjJKS0uBOezr60tJSamvr0cikVgstry8nIWFJTY2Fqh+FAq1vr4+MzMDlP76+joCgZiZmenu7h4YGAD95UG7YNDfGGj83d1dBAIBekkCS7C/EzJ4IXd2dubm5kAb4d3d3bW1ta2trfX1dSQSicfj0Wg0IccK5gWFCQgEAujcgoICJiYmJycngFqdnZ0FbYffvHlz8eLFvLy87e3t9fV1YFkBfhZ0DAZGAoPBIJFIUNoI/YME/t27dwc1OBKJhMFgfn5+gKu7srKysLCQsJsHYLYwGIyLi4tgVzAYDCH/gMFgfHx8pKSk6urq8Hj83t7e11KcgLYmNDSUi4vr3bt38/PzPj4+GRkZ3/eVf1VaW1ujoqK+0f3Uzs6Ompr6L+Dq/3fJH8pv1tfXy8vLm5ubz8/Pl5WVnT17NjExsbe3l4aGxsjIaHt7Oy0t7cSJExcvXnz69KmOjg4zM/Pk5GRISAgxMTGIpCQlJX19fcPDw6WlpSsrKwEV0M2bN0Gz4xs3btTW1m5sbLi5uYmIiJSUlJSUlDAzM2tpaU1MTJiamkpISBgaGnp5eTU3NyORSBcXF01NzaGhoYSEhF9++SU6Onp4ePj8+fMnT5709/c3MTGhpKR88eIFWDzB3ZudnaWiorKwsLC2trazswPkKGZmZgkJCTQ0NKDOxMbGRkdHByxPWFi4u7vbz89PUVGxoaEhNjaWiIhIVVV1eHiYiorqxIkTIiIiNDQ0WVlZ5eXlCgoKUVFReXl55OTkQkJCB+FN4eHh3Nzczs7Ourq6QkJCEAR1dXXR09O/ffvW0tLy0aNHk5OTnp6egNlMTk7Ox8enoqLi5MmTtLS0bm5ujo6Oly9ffvfuXXd3Nxsbm6mp6d7eXkpKCi0tbWFh4dramrKysoqKirKyspSUVGlpaUBAADExcUBAwNzcnISExLFjx2JjY78Yp4Obs7m5mZWVpaOjc/z4cXd3d6AL7t2798svv4iKik5PT29vb8fHx0tISCgrKwP6vpaWFi0trWvXrjExMRkZGY2MjDx58oSdnb2kpOTatWtycnKRkZEwGIyenj4nJ6e7u1tERISKioqbm1tcXJybmzsjI+P9+/cCAgLa2tqzs7O1tbX37t17//59aWkpAwODi4tLUlKSuLg4Pz//4ODgZ2vOzMykp6dXV1cHuDweHh4TExNlZWUlJaWqqqrXr1+zsLB4eHhsbm76+fmJiorq6+uLiYnx8vKWlJRAEBQUFMTLy/v+/fu+vj59fX13d/fJycn19XUdHR0pKamgoCBnZ2crK6vm5mbgMRgaGj58+DA6OjotLW1tbS0hIcHCwkJfXz8/Px+NRmdlZZmZmRUVFR28twEBAX//+9+NjIwmJyczMjIiIyNBjhiLxba0tISGhr59+5adnR0wieBwuPHx8ZycnJycnPfv3y8uLm5tbeno6GhraxcVFZWVlTU1NX0RuIpGo2tra4uLi0VERGRkZMbHx0dGRvLz8zc2NkDx29zc3O7ubk9Pz+Li4t7eHhqNBip+e3t7cnISUItCEAQIT0GHYSwWOz8/r6urKywsTACxgnQcKLPG4/FIJFJDQ0NKSgoYOUKQQcjagXGwWCwGgwFJTAwGc9AKAsFgMDs7O6AfBGEcgH4lHI9GowmtkgmJC3A54MT9u2f7TwTLwB9olPJP5Q/pTSsrKz4+PoAC+X/sfXVYVdu39j6hHpVjoCIhSneDKAgKEoJ0d29pNl3SXdIlXQIignQj3d0lXcIGpFNY3x/zufvhQz3XOOfc33Ov4y9Ye6055157rTHnGPMd7+vi4nL79u2xsbGKigocHBywrDM1Nf31119tbW07OjqePHmip6d3cHDw4sULbGzs1tbWgoICU1NTT09Pfn5+CwsLCIJ6enoePHhgZ2fX1tZGQUFhaWm5v7/f0dHBw8MDSKKKi4tJSEiCg4NnZmaYmJguXLhw9uxZQB6ckJDAxsYGKHwSExNJSUk7OjpiY2MvX74sIyMzMzOjoqJy9+5dQAQAHYvsVlZW2NnZaWhosrOzkUhkQEDAnTt39PX1tbS02NnZnz9/7uXlxcTEBMpyx8bGBgYGgoODCQkJ7ezsIAgqKCi4cuUK0EXAxMSkoaEpLCzs6Ojo7u6WkZFRV1dfX19vb2+np6c3MzM7ATBobW0VEhIyNjZOTU1lZmYG9yclJeXixYvy8vLPnj0DBZEODg7nzp2zt7dvamoqLi4OCAi4dOmSn5/f3NxccXHxtWvXAHMwMTExir4MFxcXlKgzMTGxs7OnpaXV19evr69bW1tjYWE1NDS8e/eOn59fQkJienr6s4kkcGRiYsLKyio+Ph4XF9fBwWF5eVlPT09DQ4OTk1NOTg6CoOzsbHp6+rCwMGtra1xc3IyMjMTERAICAktLS1D38u7dOyUlJWZmZiMjI2dn5/r6+qmpKcByXVBQUFlZef78eVJS0rq6uoKCAk5OTjgc/vr1axwcHAUFhfn5eS0tLUZGxqGhofLy8itXrhAREWlpaZmbm1+6dOl4zQUYbUlJCTk5ubKy8tbWVlJS0unTpy9duiQqKoqPj8/IyHj//n0YDCYjI/Px48enT5/+9ttv6urqJSUlfHx8QkJCk5OT+vr6LCwsExMTk5OTfHx8tLS0W1tby8vL5OTkvr6+WlpacnJyZWVlU1NTurq6UlJSxcXFysrKxMTEMTExdXV1DAwMiYmJCAQCgUDMz8/b2tri4uJmZWWdGCQEQUJCQtjY2Glpad3d3WJiYg8fPgQL+ezs7EePHjk7O2toaBASEgLqk7CwMElJyYCAAAUFBVpa2ry8vHfv3tHR0UVFRbm4uHBzcycmJn4KXJmenlZSUjI3N9fS0vr9999dXV17e3sfPHggJiY2NTWVk5PDysoaHx8PqEkkJSX9/PxAkeLi4uLg4KCampqbm9vu7m5FRYWEhISsrCw7O7uIiEhxcbG7u/sff/xBT09fXl7+8ePH/Px8dXV1KSmpO3fugFVLa2srJyenmZnZixcvqKiozM3Nj46O5ufnFRQUhISElJSU1NXVe3p6EhMTmZmZw8LCYmJihIWFg4ODUcAM1APZ2dkpJycHii/Bm9vV1aWtrf3w4cPQ0FCQQ2tvbwcsJ+D5hP6LL8rc3NzY2NjAwKC8vLympsbb27u2traxsdHDwwNMCQMDA6GhoeHh4UlJSaWlpd8E2f5+vzkzM8PGxqagoABBUGpq6s2bN83NzdfX1x0dHe/fvw9EellZWQGDbGFhIQUFBRDMqK2txcXFdXd319fXLy0ttbe3v3v3bm1tLQRB7u7u5OTkhYWFaWlpmJiYmZmZEAR5eHjQ09ODcl0jIyMyMrLm5uaioiJsbGx5eXl0dHTAeygtLS0lJbWzszM2NsbPz8/Hx/f+/Xt1dXVApNbd3U1ERGRgYICiwAK/zcHBweTkZG5uLgUFhays7OrqqrGx8dmzZ588eZKamtrb2wv4AcXFxY/X6khKStLS0vb39x8eHgLZj4GBgbCwMHR0dECQDEGQl5cXBQVFeno6BEFgAZienn6int3V1fXixYusrKze3t4ZGRmzs7NLS0s6OjqXLl3CwsIKCgoC+2BTU1OCgoLU1NTNzc3j4+MSEhLk5OSgbCM0NPTq1at5eXnOzs6srKyTk5Pv3r2TlZVVVFQEXQQFBd24ccPKympzc3Nubo6Tk1NYWPjw8DA3N5eEhCQqKupLGwvgSFtbGzMzc1NTEwUFBahccnR0tLOzo6amdnFxWV5ehsPhuLi4urq64uLifn5+y8vLExMTPDw8nJychYWFSCSytrb25s2bf/zxBykpKarURFJSUkxMbGlpKT09nZKSElAITkxMEBMTq6qqgtkxOTl5bGyMhIRETU3t6OgoMTHx7Nmz/Pz8FRUVYBV5fJcGjDYjI4OcnDwrK2tzc9PR0RENDc3V1dXc3PzMmTMaGhoODg7o6OiWlpaAY+XOnTsAwQaHw3l4eHJycsAKdH9/v6KigpiYWFlZGZCNXrp0iZKSUkNDA1QWeHt737hxIzIy8vDw0NLSEgMDY3R0dGBg4Pr16w4ODrm5uU1NTbOzs6Kiovfu3fv0bXz//j09Pb26uvrGxsbg4CAvLy8fH9/+/n52djY3N3d4ePjMzIypqSkvL293d3djY6OcnFxAQMDY2Ji2tjYmJmZvb296ejopKamampq7u3tGRsbMzMyJnw+wnGhqara3twNmo7y8vK6uLkJCQh4eno2NjeLiYkCSbWVlJSgoyMXFlZ+fb2RkhI+Pn5WVNTU1paOjY2xsnJWV9fjxYx8fn4aGBkpKytu3b09OTtrY2KChoUVFRQExAgEBgYSEhPLycmxs7Dt37kxPT8fHx4uLizs6Omprazs4ONTV1RUWFkpJSdnZ2ZWWljIxMXFwcCCRSDc3NxgMxsfHByIVVVXVEzv+6+vrIKZ0cXGRkpLKyMjIy8sD9EVSUlI8PDz9/f2NjY1SUlJOTk4mJiY4ODgNDQ3b29ve3t7y8vI5OTkaGhrY2Ni5ublhYWFXrlx58OABKSkpBQXF6OhobW2tiIiIlZWVoaEhPj6+o6PjN2H+vt9v9vX1MTMzU1NTOzo6EhISwmAwZWXlyspKCgqKK1euREREJCcnU1JSurm5QRBkbGwMg8GEhIQmJiYWFhZwcXExMDB8fX23traMjY2JiIhCQkLs7e0vX76MiYkZGRkJh8NPnz4tLi4+Ozuro6Nz7do1Hx+foKAgEJ++evXKxcWFhYWlqamJhYWFg4PjyZMn586dk5SUrKys1NLSgsFg/Pz8hYWFxMTECgoKa2trgYGBv/32Gz8//wmwZ2trq4KCwsrKCgKBoKOjKygoEBYWxsXFzc3N7e7uBhIOHBwc0tLSe3t7Y2NjCQkJeXl5TExMoqKi4F8sLCw6Orq6ujoVFRUKCgpU8CgiIsLKyvr+/fv6+npycnJcXNzy8vITz7esrOwvv/xiZ2c3MTExOjra3d09PDxMQ0Ojrq7Oy8urrq4+NjZWUlIyPj5eVFR09uxZHR2doaEhGhqaJ0+egA2f27dvc3Fx1dTUiIiICAoKQhBUWlpKRUXl5eX17t271NTUiYkJFRWV+/fv9/b2FhQU3L59287ObnZ21sXFBQsL668hXDs7O6mpqZKSklNTU4qKihgYGJycnGNjYzY2Nri4uNXV1X19fZycnJycnOHh4TU1Nbu7ux8/fjw4OEhLSyMiIoLD4Zubm/Hx8ZiYmIKCgtevXwc3/927dwQEBL6+vhAEWVhYsLCwgOMxMTF//vknYNJlYGBobGx0cnK6efMmqBvR19fHwsKqqqpqaWkhISGJjo4+scja2NgA7IUfPnxYWlri5OR8+PAh4NnDwsKqqKjw9PSkoqJqbW1tbm5mYGAAnNlbW1vMzMwWFhYBAQGPHj0CuT8/Pz9cXFyQnzU1Nf3zzz9hMBh4sYeHh+np6SUlJcE8pKSkJCoqCgagoqKCg4MTFhYGQVBNTQ0dHd1nN0bevHlDT08PJntAhh0QEDA6OsrHxweHw8HbKyQkZGBgMDAwIC8vLycnt7m5OT8/r6SkJCMjs7KyAjixTp06FR0dDdo8/lytrKw4OTmxsrICShpTU9OHDx8ODQ2BfiMiIgAb4ZkzZ2RkZJqbmwUFBcF6Ij09nZGRMTo6ur6+HoFAZGRkiIiI6OrqglwBiBg2NjYUFRVZWFhWVlby8vKIiYkDAwPBaoCWlvbp06cQBJmbm2NjY9PT0zs6Ou7v74OsgrS0NMCx0dPTm5qarq6uamhowGAwS0tLIKNga2uLyjYc/RfYRkVFhZycPDc3t7Ozs6GhQUJCwtXVNSsri5OT08bGpqmpSU5OTlFREYlEjo6O+vv7j4+Pp6Sk0NLSvnz5EoIgNzc3Pj6+kZERX19fGAzGxMQUGhqal5dXUVHx4MEDJyenwcHBFy9eXLlyxdXV9S9ehE/t+/eFPnz4EBYWJisr6+Tk5OnpqaenFxQU1N7e/ujRIz4+vsLCwvz8fCcnp5aWlr29vefPn6uoqABA4vLyMgkJiZKSEtjGzcvLExUVFRUVtbS0VFBQ4OTkzMzMtLCwoKSkNDU1XVpaSkhIuHfvnpCQkJmZGT8//+PHj/Py8kAV6tramo+PDwMDAxwOl5KSevDggYmJib6+PthuKi8vv3Pnzps3bz5+/BgUFERCQqKpqTk+Po76Fvv7+5mZmQQEBPz8/BwcHECH3s7ODpCmqKqqBgcHDw8PBwYG0tHRCQsLP3nyJDQ0tL29XVlZ+cKFCwoKCqqqqmfPniUlJY2IiBAQEDAzM0PtsQC2NBEREWlp6StXrsBgMPAYHb+NLi4uaGho4uLiNjY25ubmDQ0NkZGR586dy83NBXzgrKysuLi4YJsIExPTFbw/AgAAIABJREFU0tKyoqLi2rVrmpqaWVlZcDj88ePHNTU1L1++vHTpEjY2dktLS05ODgwGk5aWLisro6amjomJ0dTUvH//fmdnJxDPkJCQyMrKkpSUBL6gqanJzc0NiA2c+JUBx5e8vPzc3JyhoSEaGlp0dHRraysJCQk5OfnY2FhbWxsNDc2DBw/KysrS09OTk5NjY2OdnJza2tpERUVZWFhqa2tFRUWZmJhKS0uxsbHV1dWDg4OtrKzQ0NA0NDTa29uFhYWlpKQgCOro6ODg4DA2Np6cnJSUlASMlufOnbt161ZOTk5RURELCwvgJ7W2tv7tt9+MjIxObGe1tbXdvn0bnP/69WswMTc3NxMSEmppab17905CQgIbG7uoqCgxMZGSkhK8xp6enqSkpOXl5bq6uuzs7IWFhZOTkwYGBtevXy8tLZ2ZmeHl5VVSUuLg4GBkZOzo6AgKCsLCwkJF0OTk5H5+fmDO6+vrY2Bg0NLSgiAoPDycgoIiICAAlSVEmZycHBUVFeArAgRLDQ0NtbW1WFhY6enpu7u7bm5uly5dys7OLisro6WlBZIzwEnFxMQsLi4+ePBAQkKCjY3Nw8Pj+OQB3E1fXx85OTlgzcjMzATU8RAEWVpa3r9/f2tra2pqio+Pj4qKqqenp6GhgYSEJCUlBYKgpKQkdnZ2OBzu6Ojo6ekZHByMh4cHMkWRkZHExMSZmZnNzc10dHS2trYfPnwAYl8gJZqUlERHR1dWVoZEIoWEhDAwMKipqUEYUV5eTkFB0dLSAkFQamoqBQXF69ev+/r6bt++zcLC0tnZmZiYSERE1NDQcDy/CUEQ0LtmY2Pj5eUFSwdMTExTU1NTU1OAGvb09MTGxj4O1RoaGuLl5VVUVAQPs5SUlJGR0dTUlKqq6s2bN0H8CkGQhYUFLS0t8D/u7u7s7Ox/oenyWfshfaHNzc3BwUEAuFldXV1fX//48WNTUxO412CSBPCUpaUlkEXu6+szNTVVVVUF1D4g79vY2Pj69euZmZmFhYW3b9+ur68PDg7m5+eDlpeWlsrLywFV3+DgYHV19draWn9//9jY2MHBwdzcXG5u7uzs7NTU1MuXL4uLi0dGRgCDzsbGRmlpKXi7BgcHs7KyhoaGjn+F/f39kZGRV69eIRAIwJ8IQdDExERUVNTxSq/V1dXIyEg9Pb2wsDDwLVpaWqytrX18fAoLC+Pj42NjYxsbG9+8eTMwMIDaPO3p6XF3d9fT04uMjHz9+rWDg8ObN29A4hw1hrGxMQcHB2VlZXNz86SkpO3t7bKyMl9f37m5ub6+Pk9PTwQCoaenp6KiIisr6+PjMzg4GBYWhoaGZmRk5OXlZWZmBrKu1dXVWlpaRkZGXV1dnZ2dioqKAQEBg4ODSkpKVlZWRkZG0dHRKysr9fX1SkpK7u7unZ2d3t7e4uLi3t7era2tampqkZGRJ0hDtra28vPzNTU1nz59ikQiY2JiPDw8pqamUlJShISE+Pn5X79+vbCw8PTpUw4ODj09PQcHh+TkZFtbW0ZGRsB95+/v39LSAsAMS0tLSkpKjIyMtra2CASCgYHBzMwsMTHx7t271NTU9vb2Wlpa2tras7OzGxsboqKifHx8enp6goKCjx49ysnJiYiIYGZmfvXq1cbGhouLCyEhoYaGxgmCibKyshs3buDh4aWlpYWFhXFxcbW0tERERBAREWVmZk5NTdHT01+9ejUkJERbWxsdHd3X19fa2pqLiwuQsXNwcJw5cyY+Pr67u1tUVPT333+Pi4srLCzEwMBISEiIj4+/fPkyOzu7tLQ0Nja2kJBQdHS0gIAAYKgDycHw8PDbt28jEIjFxUVNTc1ff/0VgUB8qq1GTEwMg8GePXs2Pz8vLy8Pg8H8/f0bGxsvXryooaEBsqKnTp0CZNt0dHRaWlpxcXGPHz+GwWBPnjzJzMy8fPlyeXl5YGAgGxubpqYmcEmot7Kzs/PixYvm5ubJycmAAc/ExKSjo0NeXh4TE7O0tLS8vBwDAwOkbpydnTExMQ0MDGZmZsAaAg8Pz9fXF+yMXblypbGxMTMzEx8f/9y5cwDXgYmJaWJiEhYWxsrKqqWlNT4+XlNTQ05OjoGBkZ+fHx0dTU9Pb2BgoKamJiIi0t7eLiIigo6O3tPT09HRwcbGduvWrfLy8uTkZCoqqpCQkMXFRTU1NQoKiqioKFSkfHR0tL6+Hh8f39DQkJWVRUpK6uLiEhwcfPny5eDg4MbGxpaWFhAKkJGRlZeXAy/R2NgYHByMhYUFNldKSkqAMmNVVRUPD4+BgQHYz+jt7b137x7ArlRXV+Ph4dnY2HxrZeMP4d6/6fylpSVfX19hYWF+fv66urqvwet+Ry9f38hXHvyaIz8ymP39/f+WBGFubg5gPpaWloD8XGNj4/EqzIODg9XVVRAu7ezsgAZRuOvu7m7w0erq6tzcHNg9X1paQonTjo6OAqWq451ubm4ODAx0dXWNjIzs7e0hkcjt7e2NjQ2g7AhWQxAELS4upqWlRUVFgdbA8gHsCC8vL29sbHR0dAAt2c7OzpcvXy4uLnZ2dmZnZy8vL3t7e5OSksrKymprawcGBgIX8/Hjx+Li4ufPn8/MzExOThYXFy8sLAwPDycnJwPGmnfv3r18+bK1tfXEsz4+Pu7r6xsZGbm9vT00NPT27dutra2SkpKIiIiZmZm1tTVfX9+QkBAQGrOzs7u5uSEQCBDQQRAUGhpqYmLS2tq6uroK6N2Ghobq6+stLCy6urqWlpbc3d0VFBSio6Pd3d3FxcU9PT39/PxERUVtbGwyMjIQCISysjIcDgc7DD4+PhISEnFxcZ9KSpibm4uJiaWlpY2Pj9vZ2fHz8yckJMzNzenp6cnIyBgYGNja2srKyrq4uGRlZVlbWwsKCgJZhIcPH5qamiYnJ2toaAC+O1lZWUFBQeA4ULawsGBoaMjJyamkpPT06VNeXl5tbW2we0NCQpKYmJiRkcHKytrd3Q34g+/duwf8e0FBAQ4OzuPHj8fHxz9+/BgcHExERKSpqQlyKYSEhCkpKYGBgSQkJPLy8s+fP9fS0qKmplZTUwN4D1JS0tzcXHNz8wcPHlRWVkZGRoLqNVVV1Vu3bklISFhZWWFhYV2/fr2srMzHx4efn7+3txcIIpCSknp7ex9HBQwMDLCwsEhISDg4ONDT0yckJBQWFpKRkRkbG4eHh5uYmIyMjBQUFAAVA2dnZw8Pj7Kysri4uNOnT4uJifn4+HBzc8NgMGtra0tLSxYWFiDRDEFQa2srBgYGHA6Pjo7m5eWFwWC8vLyAduDr7e+ss/wLOzo6Gh8fNzMz09bWRu1o/7Rvsr29vaioqN9++42Hh+c/U9L6m2xmZgYUEQGW5X/NYmJiyMjIkpOTjx/8JgwKBEFbW1uHh4egfhEcAWAdFOvlhw8fwPr9BFbh8PAQkHtCELS/vz88PIyavVZXVwGoGfChgcsXFhaAOvH+/v7AwMD29vbKysr8/DzA9PT3909PTx8fPOhraWnp+fPnZWVl6+vrZWVlnZ2dq6urmZmZOTk5Hz9+7O/vB+ioo6OjyspKsFsLQZCLiwsPDw8QE4cgaGpqKigoyNvbu6urq6Gh4cWLF1NTUzMzM+Hh4bm5uXt7e42NjUZGRkZGRuXl5RUVFSkpKUgksqSkJCEhYW1tbXZ21t/fPzk5+f379/7+/kAf1MfHx9HRcWJiorq6OjU1dXd3d35+3tXV1cbG5sTqYWJiwtraWl1d/cmTJ2BpvLGx8ezZM15eXnFx8YSEhPX1dSQS6eTkxMfH9/DhQ5ATWFpagsPht2/fFhMTMzExkZOTi4uL8/X1tbW1RaFNgXgcOzu7oqKihYUFFxcXGxvbt5JG/ht+8+joM+rMP+1bbWVlJSAggJ2dHYFA/HMUUP+apaWlMTAwiIiIoMLMH7Gjzwmjo46g0Hn9/f38/PwA3PrpaSfaOQ4GPPHHp71/6d/jwMATL8KnxU7f9H0/e/C/xSGewEhCELS7u1tfXx8bGyslJQU2mv6nXtgT+c2vPPnTIyAH+NlLUM9Da2srKnMIUnnfFEf+e+vNf6ej7zDAx/fPtf93NX68na9s88Qln772X3IEP2hf00tXV1deXh4geP9bejzRy9EnBkFQdXU1yNger8854Ra/6d9Pu/7078+6gy9dgjrtrw9+TbMn7s+X/picnBQSEiImJgbY579o5LMNfsenXzrtL676dEhf2cVfN/LdDf5LfvM/0z58+FBWVhYVFVVfX/+3r+A2NjYmJiY+q7Hzr9nR0dHm5ubS0hKopvgshxsoOlxeXgbben9Xv6D6ENSBfEkl5m/p61tHBcpIvpsz6X+fHR4ednZ2AlkU6J/kmvvfZP/DfhMUQn335Se4JL7JVlZWfHx8QOW4np7ep3iRH7Tk5GRQI//Xp/2Nz+j29vby8vJx+O7+/n58fLyKikpbWxv0hSze3t5eXFyckpJSSkrKD/L+HbepqanXr18XFxcDvpX/wFfxnxjS3t7exsbG1tbW9z3VOzs7f82X8U8birrtxEr5p52wH+L1+Is7e3QsRfKleGR4eDghIeG4isg3hR4rKyuOjo6fJYX+tMFPj6SmpvLw8FRWVo6Pj8/NzZ2g2/hxCw4OxsTE/As87dLS0uTk5KeSQUf/lYL5kt73l0YYHx8P0K+oI9vb2wgEgoaGBpRjffbCnZ0dfX39P/74Iz09/W98T1paWlhZWeXl5f8TUrHLy8stLS1ARu3r3cF3OI6ioiJBQUFLS0uQfPimy5FIpKurq46OTkBAwGdpN7/Djr698hqCILAHlZeX19bW9ike4D/WTjiNj/9l/8QK+ofwmwsLC1VVVWALf2Jiorm5eXt7u6GhobW1FUAKZmZmUMX/Hz58KC4uLikpASmtkZERFRWVx48fo0pWZmdnAYsH9MktgCBof3+/vb0d5WRHRkbMzMzu37+Pqs+ZmZkZGRkB2JcT1346clAXDCDKqOEBTcfvuyGfmqam5s2bN1HSzCdsa2tLX18fQPc//XRvb09TUzM1NfWbntr29vaYmJjjBVGbm5syMjICAgJ/QYm/vb0NVG3/lv0ZlKWlpeHj45uamv6NbX635eXlUVNTe3h4fOX5+/v7CwsLf00T9VkD8H4DA4NvxQPOzs6amJiIiYkZGhq6uLh8ivr8bnv9+nVkZCRq1/5rbH193cvLi5iY2MnJ6e+Sujs6OkIikX19ff8cffKJea6xsVFZWdnNze3vmoSO2w/F6U1NTXx8fEpKSrm5uWJiYnR0dCoqKsLCwvT09M3Nzfv7+0+ePDE1Nd3d3S0tLZWSkjIxMQEcnfHx8a6urhcuXKCnp+/o6Njd3fXy8lJRUbGzs+Pk5JSVlT3hPRcWFuzt7fn4+MTExKSkpFJSUuLj469du0ZKSlpcXLyzs+Pm5iYlJaWkpMTKygqKlEDZwObmJqjXPl5QCIZ99uxZVVVVILnu5+enqKgIsNajo6PNzc3Kysqenp7R0dFqampv375VUVFRVFSMjY0Fx1tbW58+fSotLQ24Qff392NiYu7fv//48WN5efnCwsLd3V0hISEGBoYv4cIsLS3/+OOPx48fT05O7uzsxMbGKigo2Nra9vb2fvjwAQ6Hw2AwTU1NAHOpqKiws7MLDAzMysoqLi5uaGgICAhIS0t7/vy5k5MTAOI1NTUlJCScYO5aX1+no6MzNDSsq6vLysoC3vPw8DA/Pz8oKAi8S5ubm3fu3BEREcnJyenv70eF6pubmxUVFY2NjRMTE3t7ex0dHXV1dXt7e5OTk4DtDbRfX18PhHlRmdyFhYXOzk5TU1MuLi6UtNb8/PyneKOxsbHjTMZ/o52YL1dWVkpKSr6+r5ycHFBJ9a39FhQUkJKSomgxPx3JZ+3g4CAyMvLOnTtgSQEElv+WjRcIggICAszNzVHLi68JX1ZXVxEIxJUrV44j6r8+7vnSxlRpaamAgAAK5/Sla7+0//PpWupTm5+ff/r0qaOjI6ABJCAgsLOzOw6n/+uhfn2E8UN+s6qqioSE5Pz589bW1np6emfOnLG0tLSysjp9+nRubi4EQZycnKqqqr29vTIyMkZGRg0NDaampufPny8sLLS0tKSgoAgLC1tfX3d2dn748GF2dvabN28ICAhYWFjApAS+AxKJBA43IyPD2Nj43LlzERERvr6+Fy9ejI+Pn5+fDw8Pf/z48fPnz11cXH799VdJScmKigpMTMxbt24hkci4uLgbN24AkDawubk5OTk5TEzMt2/fLiwsWFpa8vDwREREuLq64uDgpKamlpWVXb58GR0d/c6dO48ePSorK2NhYQGODAMD4+LFi2ZmZnfv3j1z5gyoYAH4Zx8fHzk5uV9//TUjI6O1tZWKisrExORL2juSkpLY2NihoaG7u7uBgYEKCgqurq5sbGxubm6jo6OYmJgcHBxlZWVHR0chISFwONzX11dGRoaVlTU0NPT58+eYmJhUVFTW1tYyMjKCgoLNzc1JSUlsbGyg6hnY4eFhTU0NFRVVRkaGqampiIjIwMDAwMCAra2tlpYWmPCAODsGBgYRERHgoQCMSqWlpfr6+g4ODvLy8p6enktLS+bm5oyMjBYWFmB2WVlZefv2raqqqomJiYyMDKDUgyAoMzNTRUVFWlr65s2bKioqq6urKysrwcHBKioqoqKisrKybm5uKysrS0tLfn5+GhoakpKS4uLiSUlJ/f39SkpKQJ1VRUVFWVl5cnIyOTlZVlY2Ly+vqKhIXFz82bNnY2NjkpKSxsbGQDve0NAQ/LIjIyMeHh4aGhpSUlLm5ubH8a2lpaW6urqJiYnj4+MxMTGALHl/f7+mpiYqKurDhw/d3d1wOFxYWBhw1zc1NZGTk58/f97DwyMrKyspKWlubi4tLa22thaU/Ofk5GxtbS0uLlZWVk5MTBx/04KDg+np6REIBJjDUMPo7e318/N7+fLlzs7O6OhoVFRUe3s7Eolsb2+vr68PCwtjZGTk4+M7Ojqam5ubn58HF05PT8/NzW1sbPT19Y2MjGxvb4NSOhRodHx8vKqqqr+/HxUnraysNDc3t7W1TUxMgBC1rq6uoaHhRDpoc3MTFQiC8a+vr4+NjYHV5fv3701MTAQEBLa2tlCwStTX/GwSfHBw8LMO7ritra3l5uZ+CSSEuvZr9s2/1MX+/v7r169fvny5trbW0NBw+/bt42mrL+UrgoKCAH7z6yP6H/Kbubm5mJiYd+7cKS8vd3R0JCcnB0QjN2/eLC8vHxkZ0dTU9PPzMzQ0ZGVlXVhY2N3d1dTU5ODgmJ+fl5WVFRISWlhY6OrqYmRkBAHdu3fvwOOLCnN2dnasra1BTSsEQfb29rS0tL29vQgEgp6efm1tbXx8/M6dO56enmA8VFRUgYGBTU1NzMzMZmZmY2NjvLy8YmJix9OgCwsLKioqjx49giCooKAAExMTUDx0dnZiYmJGR0enpqaeOnWKg4MjOTm5ra1tfHycnp6ejIzs1atXzMzMp06dcnd3FxMTo6Wl7enpycjIoKSkBBW+3t7eDAwMfX197u7uoJ4X+txvPDc39/DhQ1FR0ampqaysLEVFxcTERF9fX2Zm5oKCgrm5uVu3bgG+ZFCX7efnh0QiZWVlKSgouru77ezsfvvtNwsLi97eXi8vrz///DMrKys8PJyOju442+PW1paNjQ1gmrG3t3/9+vXc3Jyrq6uWllZ6ejobGxs7OztQNyEnJ3d2dk5JSSEkJBQTE8vJyZGXlzcyMoqLi8PAwHjy5Mni4qK0tDQMBmNlZRUTE0tOTi4uLhYUFDQyMkpNTSUjI8PGxu7p6QkODubg4ADFG9evX7exsdnZ2XF1dRUREYmIiFBSUoLBYEpKSiMjI7q6uoqKii9evBAWFobBYJGRke3t7efPn8fExFRRUeHl5T179mx1dTWgYyAnJzczMyMnJ799+/bExAQ9Pf25c+fGx8c3NzcB5/nIyIixsbGNjY2FhQUaGhoDA8PxMDkxMREGg+np6XV0dAgICAD60ZWVFVNTUzgcDoqXHz58yM/PLygo2NHRAQhVTUxM8vLylJWVCQgIALuEi4uLq6srPj6+jIzM/Px8ZmamgIBAa2sr6vfd3t4WFxcnJCQ0Njbm4+Pj4+Pr7e1dWVkJCwsD1a4MDAxpaWmZmZmMjIzy8vLgm0ZFRZmZmaGhoZmZmRUVFQkJCYHHdWZmRkdHB1RYGRoaamhopKSkSEtLCwgI5OXlbW9vP3/+3NbWNigoSE9PT0FBIS4urqGhwcXFxc7OTltb287Obnh4OCAgQFpa+niwtbOzU1JSYmRkpK+vb2RkBLZDo6OjEQgEKFJaWVnp7+/n5eXFxsZ+9OiRqKhodnY2WLINDg66uroiEAgDAwNXV9fR0dGlpaVnz55ZW1vLycnB4XAbGxvggN6/fx8eHm5paamvr29vb19dXf3q1StbW9vKykrUXLKzs5Obm+vo6Ojj42NhYaGnp1dbWws+ra6uDgsLs7OzKygoAMTe4eHhi4uLzc3NHh4eIHBZXl5OSkpSU1MzNDQEZWDt7e1hYWGvXr0C2S0vLy8FBYWUlJT09HRU/gqJRCYlJT1//rympqampmZwcDAkJOTatWva2tqLi4v/0nrTwcEBBwensLBwfHz8/v37wPctLCyQkZGFhIRYWFj4+/tnZGQwMjKCbeXa2loiIiIvL6+mpiZ8fHw3N7ejoyNra2sWFpaOjg7AYn3//v3juZja2lpMTExtbe2jo6O+vj4uLi47OzvAP2hhYQFCWiIioo6Oju3tbTU1NW5u7omJiczMTGpq6pqamtDQ0AsXLkRHRx9PFKanp5OQkAC2Pi0tLRYWFpDFd3R0PH/+fGhoqKam5nG5t7S0tHPnztnZ2dXU1JCSkioqKpaWlgoLC9vZ2U1PT6OIiJBI5P379zU0NGZmZkRERMTFxY9nqVA/ydHRUUFBATo6ekBAwIcPH4SEhCgpKUGxeWxsLAiir1+/DshAOTg4NDU1l5eXx8bGHj58qKGhsbGxoa6ufvfuXVC87+TkREdHV1RUpK+vLyQkdHydvra2JikpiYGBAYPBwNNcXl7OyMgoJCTk5+dnampaVVW1vLysqqoqKCgIckC8vLyioqKampp4eHimpqbW1tZaWlpVVVXz8/NsbGwXL14ETgqJRAJfs7y8PD8/z8nJyc/Pn5+fT0JCYm1tDTh979279/Lly6ysLBoamsTERAiCUlJSiImJQTEcExMTyPza2NhQU1MPDQ0VFRVdv36dhIQkJCQEgUAICAiMjIx4e3v/8ssvzMzMUVFRsrKywsLCe3t7fn5+WFhYwLOIiIhERkYaGhpKSUnNzs4ODg4+fPjQ1tb2+HozJiaGlJQ0NTV1Z2cHsN4lJyfX19czMjL6+voikUgSEhJOTs6ioiJAPWVtbY2Dg9Pb2zs/P09AQPD777/r6Oh4eHhUVlb6+/v/+uuvysrK8/PzcnJyREREx3NnfX19t27dEhMT6+rqsrOzw8PDi46OLigo4OHhSUtLs7KywsDASElJSUlJwcDAICUlVVVVtba2rqqqsre3x8XFbWtrAyxK2NjYvb29L168ICMje/HixeLiIg8Pz2+//WZoaKipqXn27Nnw8PCUlBQ2NjYfHx9A/PzLL788f/48JibmypUrQCPAw8NjZGREXFz88uXL4FaDp2JiYgJMwN7e3mRkZP39/aWlpYKCgq6urnR0dOTk5Kurq9XV1VevXuXg4FBRUcHHx1dQUEAikV1dXVpaWjo6Op6enrdu3SIlJW1sbEQgEHh4ePb29mFhYRcuXLhx40Z+fv7IyIiVlZWqqqqLiwslJSUaGlpFRYWrqysMBgsMDAQR2NHR0d7enouLCwwGe/jwIQKBYGVlBQupFy9emJmZRUdHU1FRCQkJra2teXh4XL582dLSUlVVlZycPCoqanFx0dbWlpeXV0tLi5+fn5iY2NzcvLy8HIQ+gIRfSEgoPDzcw8ODh4fH1dV1enp6YGAAgUCYmJjY2dnx8fFZWFg0NzffvXv3woULAQEBYBX/j/vN5eXlR48eAZdRUlJy5swZWVnZiYmJ9+/fk5OTExISqqur9/f35+TkUFBQGBgYvHr1iouLC9CmRUVFXb16VVVVFYlEysjIUFJS1tXVAR939erVkpISlJsLCws7deqUjY1NZ2cnHA7HwMAICQnJzs7+5ZdfVFVVOzo6aGhoSElJ8/Pzg4ODT506RUdHV11d7eLiQkxM/OrVq1u3bsFgMC8vr+PbL8+ePcPBwSktLR0bGxMQEFBWVoYgaG5ujpqaGsT7gEIYnDw7OysrK0tCQtLY2Ojg4HDjxo2SkpLY2Fg8PDwLCwtra+vLly8/e/Zsb28vPDz8zz//NDMza21tBcoZYJt+aWkJ0HmAn+Tg4MDDwwMfHz85Obm3txdw8SUmJjY2Ng4NDQFXTkFB0dbWlpGR8eeff4ICag8Pjxs3boSGhg4MDNy5c8fLywv8BJycnAgEAqVWAtZZoCNwprq6+uXLl2NjYz9+/AioBg0NDcPDwzs7O0GdHxMTk7Oz8/7+fkNDAxsbm4mJiYSEBA0NzfPnzyMjIycnJ4+Ojurq6q5evQqHw0HUVlBQcPfuXUAEl52dTUdH5+joaGBgwMnJOT8/f3h4CJZF7e3tOjo6d+/ePTo62t3d1dXVffz4cWtrKw8Pj7OzM4hJ2djYJCUld3Z2HBwczp49m5CQsLy8TE9PHxgYeHBw8OjRI3Jy8rq6utTUVGpq6oSEhKOjo8DAQDw8vKG